Optical multilayers
Patent Information
- Application Number
- JP2023109414
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-07-03
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2040-03-31
Smart Images

Figure 0007634043000006 
Figure 0007634043000007 
Figure 0007634043000008
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate suitable for encapsulating light-emitting elements in self-luminous display devices such as mini / micro LEDs. [Background technology]
[0002] In recent years, self-luminous display devices, such as mini / micro LED display devices (Mini / Micro Light Emitting Diode Displays), have been devised as next-generation display devices. Mini / micro LED display devices are basically configured such that a substrate on which numerous tiny LED light-emitting elements (LED chips) are densely arranged is used as a display panel, the LED chips are sealed with a sealing material, and a cover member such as a resin film or a glass plate is laminated on the outermost layer.
[0003] There are several types of self-luminous display devices such as mini / micro LED display devices, including a white backlight type, a white light-emitting color filter type, and an RGB type, and in the white light-emitting color filter type and RGB type, a black encapsulant may be used to prevent reflection of metal wiring arranged on the display panel substrate and metal oxides such as ITO (see, for example, Patent Documents 1 to 3). In particular, in RGB type mini / micro LED display devices in which LED chips are arranged, the black encapsulant can also contribute to preventing RGB color mixing and improving contrast. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-204905 A [Patent Document 2] JP 2017-203810 A [Patent Document 3] Special Publication No. 2018-523854 Summary of the Invention [Problem to be solved by the invention]
[0005] When the black sealing material is used, the upper part (image display side) of the light emitting element such as the LED chip is covered with the black sealing material with reduced transmittance for visible light, which causes a problem of reduced light emission efficiency and dark images. In order to address this problem, if the output of the LED chip is increased to increase the light emission brightness, there is also a problem of increased power consumption.
[0006] Increasing the visible light transmittance of the black encapsulant in order to improve luminous efficiency results in a trade-off between the anti-reflection function of the metal wiring mentioned above, the prevention of RGB color mixing, and contrast, all of which are reduced. Achieving both of these goals has been a difficult challenge.
[0007] On the other hand, liquid curable resins and adhesives containing black colorants (dyes and pigments) are used as the black sealing material. When liquid curable resins containing black colorants are used, there is a problem that unevenness in the blackness occurs due to uneven thickness. In addition, pigments are often selected because they are superior in both heat resistance and weather resistance compared to dyes, but when liquid curable resins with dispersed pigments are used, in addition to the uneven thickness, problems such as uneven filling when filling the liquid curable resin and uneven dispersion of the pigment during flow occur. In addition, since the surface of the cured liquid curable resin after sealing has no adhesion, it is necessary to further laminate a cover member using an adhesive or the like, which also causes the problem of requiring additional labor and materials.
[0008] The present invention has been devised under the above circumstances, and an object of the present invention is to provide an optical laminate suitable for manufacturing a self-luminous display device such as a mini / micro LED display device that has improved contrast and anti-reflection function such as metal wiring while increasing luminous efficiency. Another object of the present invention is to reduce the number of steps and necessary materials in the manufacturing process of the above-mentioned self-luminous display device. [Means for solving the problem]
[0009] As a result of intensive studies to achieve the above object, the present inventors have found that by using an optical laminate in which two adhesive layers having different transmittances are laminated and further laminated with a substrate in the manufacture of a self-luminous display device, it is possible to manufacture a self-luminous display device having both improved luminous efficiency, an antireflection function such as metal wiring, and improved contrast. Further, by using the optical laminate, it is possible to reduce the number of steps and necessary members, and it has been found that a self-luminous display device with improved luminous efficiency, an antireflection function such as metal wiring, and improved contrast can be efficiently manufactured. The present invention has been completed based on these findings.
[0010] That is, a first aspect of the present invention provides an optical laminate having a laminated structure in which a first adhesive layer, a second adhesive layer, and a substrate are laminated in this order, and the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2.
[0011] In the optical laminate of the first aspect of the present invention, the fact that the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2, that is, the configuration in which the visible light transmittance of the first adhesive layer is lower than the visible light transmittance of the second adhesive layer, is such that when the optical laminate of the first aspect of the present invention is used in the manufacture of a self-luminous display device, the first adhesive layer is preferable for preventing reflection by metal wiring or the like on the display panel, preventing color mixing between the arranged light-emitting elements, and improving contrast. Further, this configuration is such that the second adhesive layer having a higher visible light transmittance than the first adhesive layer is located above the light-emitting element (image display side), and it is suitable in that the luminous efficiency can be improved to brighten the image, and the power consumption due to the output increase for increasing the luminous luminance can be reduced. That is, the optical laminate of the first aspect of the present invention, by having this configuration, solves the problems of improving the luminous efficiency, and at the same time, the antireflection function of metal wiring and the like, which is in a trade-off relationship therewith, preventing color mixing of RGB, and improving the contrast.
[0012] In addition, by using the optical laminate of the first aspect of the present invention in the manufacture of a self-emitting display device, the laminated structure of the first adhesive layer and the second adhesive layer serves as a sealing material for sealing light-emitting elements arranged on a display panel, and the base material becomes the outermost cover member. Therefore, there is no need to separately laminate a cover member after sealing, the number of processes and required members can be reduced, and the manufacturing efficiency is improved.
[0013] Furthermore, the configuration in which the sealing material for sealing the light-emitting element is an adhesive layer composed of the laminated structure of the first adhesive layer and the second adhesive layer is such that when the light-emitting element is sealed with the adhesive layer in the manufacture of a self-emitting display device, unevenness in blackness due to the above-mentioned thickness unevenness, filling unevenness, dispersion unevenness of pigments, etc. is less likely to occur. Moreover, it is suitable because it can prevent reflection of metal wiring, etc., prevent color mixing of RGB, and improve contrast.
[0014] In the optical laminate of the first aspect of the present invention, it is preferable that the visible light transmittance T1 of the first adhesive layer and the visible light transmittance T3 of the base material satisfy T1 < T3. This configuration is preferable in terms of improving the above-mentioned luminous efficiency.
[0015] In the optical laminate of the first aspect of the present invention, the visible light transmittance T1 of the first adhesive layer is preferably 80% or less. This configuration is suitable in terms of further improving the above-mentioned reflection prevention function of metal wiring, etc., preventing color mixing of RGB, and improving contrast. Also, the visible light transmittance T2 of the second adhesive layer is preferably 85 to 100%. This configuration is suitable in terms of further improving the above-mentioned luminous efficiency. That is, the visible light transmittance T1 of the first adhesive layer being 80% or less and the visible light transmittance T2 of the second adhesive layer being 85 to 100% is extremely suitable for achieving both the improvement of luminous efficiency and the reflection prevention function of metal wiring, etc., the prevention of color mixing of RGB, and the improvement of contrast, which are in a trade-off relationship with each other.
[0016] In the optical laminate of the first aspect of the present invention, it is preferable that the first adhesive layer and the second adhesive layer are adhesive layers formed from an adhesive composition having a composition selected from a photocurable adhesive composition and a solvent-based adhesive composition. The adhesive composition forming the first adhesive layer preferably contains a colorant. These configurations are suitable in that T1 and T2 satisfy T1 < T2, and further improve the above-described luminous efficiency, antireflection function such as metal wiring, prevention of color mixing of RGB, and contrast.
[0017] In the optical laminate of the first aspect of the present invention, the adhesive composition preferably contains an acrylic polymer. The acrylic polymer preferably contains a (meth)acrylic block copolymer. The adhesive composition forming the first adhesive layer is preferably a solvent-based adhesive composition containing a (meth)acrylic block copolymer. These configurations are such that when the optical laminate of the first aspect of the present invention is used in the manufacture of a self-luminous display device, the first adhesive layer and the second adhesive layer (particularly, the first adhesive layer) are filled in the steps of the light-emitting elements arranged on the display panel without gaps, and are excellent in step absorption and processability.
[0018] In the optical laminate according to the first aspect of the present invention, the thickness of the first pressure-sensitive adhesive layer is preferably 10 to 300 μm, and more preferably 15 to 200 μm. The thickness of the second pressure-sensitive adhesive layer is preferably 1 to 500 μm, more preferably 10 to 300 μm, and even more preferably 15 to 200 μm. The ratio of the thickness of the second pressure-sensitive adhesive layer to the thickness of the first pressure-sensitive adhesive layer (thickness of the second pressure-sensitive adhesive layer / thickness of the first pressure-sensitive adhesive layer) is preferably 1.0 to 5.0, more preferably 1.2 to 4.0, and even more preferably 1.3 to 3.0. These configurations are preferable in that the first pressure-sensitive adhesive layer sufficiently seals the spaces between the light-emitting elements arranged on the display panel of the self-luminous display device, thereby preventing reflection of metal wiring and preventing color mixing of RGB to improve contrast, and the second pressure-sensitive adhesive layer, which has high transparency, covers the upper part (image display side) of the light-emitting element, thereby improving luminous efficiency.
[0019] In the optical laminate of the first aspect of the present invention, the surface of the substrate on which the second pressure-sensitive adhesive layer is not laminated is preferably anti-reflection treated and / or anti-glare treated. The anti-reflection treated and / or anti-glare treated is preferably an anti-glare layer provided on one surface of the substrate. The anti-glare layer is formed using an anti-glare layer-forming material containing a resin, particles, and a thixotropy-imparting agent, and the anti-glare layer preferably has an aggregate portion in which the particles and the thixotropy-imparting agent aggregate to form a convex portion on the surface of the anti-glare layer. In the convex portion on the surface of the anti-glare layer, the average inclination angle θa (°) is preferably in the range of 0.1 to 5.0. These configurations are preferable from the viewpoint of imparting an anti-reflection function and / or anti-glare function to the surface of the optical laminate of the first aspect of the present invention, preventing a decrease in visibility due to reflection of external light or reflection of images, and adjusting the appearance such as glossiness.
[0020] The optical laminate according to the first aspect of the present invention may further include a surface protection film laminated on the surface of the base material on which the second pressure-sensitive adhesive layer is not laminated. Such a configuration is suitable for preventing scratches and adhesion of dirt during production, transportation, and shipping of the optical laminate and optical products including the optical laminate.
[0021] Further, a second aspect of the present invention provides a self-luminous display device including a display panel having a plurality of light-emitting elements arranged on one side of a substrate and the optical laminate of the first aspect of the present invention, in which the surface of the display panel on which the light-emitting elements are arranged is laminated with a first adhesive layer of the optical laminate. In the self-luminous display device of the second aspect of the present invention, the display panel may be an LED panel having a plurality of LED chips arranged on one side of a substrate. Such a configuration is preferable in that the self-luminous display device of the second aspect of the present invention can improve the light-emitting efficiency while preventing reflection of metal wiring on the substrate, preventing color mixing of RGB, and improving contrast. Effect of the Invention
[0022] By using the optical laminate of the present invention in the manufacture of a spontaneous light emitting display device, it is possible to efficiently manufacture a spontaneous light emitting display device having improved luminous efficiency, anti-reflection function for metal wiring and the like, and improved contrast. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is a schematic diagram (cross-sectional view) showing one embodiment of the optical laminate of the present invention. [Diagram 2] FIG. 2 is a schematic diagram (cross-sectional view) showing another embodiment of the optical laminate of the present invention. [Diagram 3] FIG. 3 is a schematic diagram (cross-sectional view) showing another embodiment of the optical laminate of the present invention. [Figure 4] FIG. 4 is a schematic diagram (cross-sectional view) showing one embodiment of a self-luminous display device (mini / micro LED display device) of the present invention. [Diagram 5]FIG. 5 is a schematic diagram (cross-sectional view) showing another embodiment of the self-emitting display device (mini / micro LED display device) of the present invention. [Figure 6] FIG. 6 is a schematic diagram (cross-sectional view) showing another embodiment of the self-emitting display device (mini / micro LED display device) of the present invention.
Embodiments for Carrying Out the Invention
[0024] The first aspect of the present invention provides an optical laminate. The optical laminate of the first aspect of the present invention has a laminated structure in which a first adhesive layer, a second adhesive layer, and a base material are laminated in this order. The visible light transmittance T1 of the first adhesive layer and the visible light transmittance T2 of the second adhesive layer satisfy T1 < T2.
[0025] "Optical" in the optical laminate of the first aspect of the present invention means being used for optical applications, and more specifically, means being used in the manufacture of products (optical products) using optical members. Examples of optical products include input devices such as image display devices and touch panels, but self-emitting display devices such as mini / micro LED display devices and organic EL (electroluminescence) display devices are preferred, and in particular, it can be suitably used in the manufacture of mini / micro LED display devices.
[0026] Hereinafter, embodiments of the present invention will be described in relation to the drawings, but the present invention is not limited thereto and is merely illustrative. FIGS. 1 to 3 are schematic diagrams (cross-sectional views) showing an embodiment of the optical laminate of the first aspect of the present invention. FIGS. 4 to 6 are schematic diagrams (cross-sectional views) showing an embodiment of the self-emitting display device (mini / micro LED display device) of the second aspect of the present invention.
[0027] In FIG. 1, the optical laminate 10 has a laminated structure in which a first adhesive layer 1, a second adhesive layer 2, and a substrate 3 are laminated in this order. In FIG. 2, in the optical laminate 11, an antireflection treatment and / or an antiglare treatment 4 is applied to the surface 3a of the substrate 3 where the second adhesive layer 2 is not laminated. In FIG. 3, in the optical laminate 12, an antiglare layer 4a is formed as an antireflection treatment and / or an antiglare treatment on the surface 3a of the substrate 3 where the second adhesive layer 2 is not laminated. In the present embodiment, the visible light transmittance T1 of the first adhesive layer 1 and the visible light transmittance T2 of the second adhesive layer 2 satisfy T1 < T2. That is, the visible light transmittance of the first adhesive layer 1 is lower than the visible light transmittance of the second adhesive layer 2.
[0028] In FIG. 4, a self-luminous display device (mini / micro LED display device) 20 includes a display panel in which a plurality of LEDs 7 are arranged on one side of a substrate 5, and the optical laminate 10 according to the first side of the present invention. The surface on which the LED chips 7 on the display panel are arranged is laminated with the first adhesive layer 1 of the optical laminate 10. In FIG. 5, in the self-luminous display device (mini / micro LED display device) 21, an antireflection treatment and / or an antiglare treatment 4 is applied to the surface 3a of the substrate 3 where the second adhesive layer 2 is not laminated. In FIG. 6, in the self-luminous display device (mini / micro LED display device) 22, an antiglare layer 4a is formed as an antireflection treatment and / or an antiglare treatment on the surface 3a of the substrate 3 where the second adhesive layer 2 is not laminated.
[0029] In the present embodiment, a metal wiring layer 6 for sending a light emission control signal to each LED chip 7 is laminated on the substrate 5 of the display panel. Each LED chip 7 that emits light of each color of red (R), green (G), and blue (B) is alternately arranged on the substrate 5 of the display panel via the metal wiring layer 6. The metal wiring layer 6 is formed of a metal such as copper, reflects the light emission of each LED chip 7, and reduces the visibility of the image. Also, the light emitted by each LED chip 7 of each color of RGB is mixed, and the contrast is reduced.
[0030] In this embodiment, each LED chip 7 arranged on the display panel is sealed without any gaps by the first adhesive layer 1 and the second adhesive layer 2. That is, the laminated structure of the first adhesive layer 1 and the second adhesive layer 2 can serve as a sealant for each LED chip 7.
[0031] In this embodiment, the first adhesive layer 1 seals the spaces between the LED chips 7 arranged on the display panel and the metal wiring layer 6. The visible light transmittance of the first adhesive layer 1 is lower than that of the second adhesive layer 2, and thus has sufficient light blocking properties in the visible light range. The first adhesive layer 1, which has higher light blocking properties, seals the spaces between the LED chips 7 without any gaps, thereby preventing color mixing between the LED chips 7 and improving contrast. In addition, the first adhesive layer 1, which has higher light blocking properties, also seals the surface of the metal wiring layer 6, thereby preventing reflection by the metal wiring layer 6.
[0032] In this embodiment, the second adhesive layer 2 seals the upper part (display image side) of each LED chip 7 arranged on the display panel. The visible light transmittance of the second adhesive layer 2 is higher than that of the first adhesive layer 1, and therefore has sufficient transparency in the visible light region. Since the second adhesive layer 2, which has higher transparency, seals the upper part (display image side) of each LED chip 7, the absorption of visible light emitted from each LED chip 7 is suppressed to be low, and the light emission efficiency can be increased, so that the image can be made brighter. In addition, since there is no need to increase the output to increase the light emission brightness, power consumption can be kept low.
[0033] The mini / micro LED display device of this embodiment can be manufactured by bonding a display panel having a plurality of LED chips arranged on one side of a substrate to the first adhesive layer of the optical laminate of this embodiment. In this case, the base material 3 can be a cover member that forms the outermost layer of the self-luminous display device (mini / micro LED display device). Therefore, according to this embodiment, the process of separately attaching the cover member can be omitted, the number of necessary materials and processes can be reduced, and production efficiency can be improved.
[0034] In the mini / micro LED display device 21 of this embodiment, the surface 3a of the substrate 3 is subjected to anti-reflection treatment and / or anti-glare treatment 4, and in the mini / micro LED display device 22, an anti-glare layer 4a is formed as an anti-reflection treatment on the surface 3a of the substrate 3. The anti-reflection treatment and / or anti-glare treatment 4, particularly the anti-glare layer 4a, prevents a decrease in visibility due to reflection of external light or reflection of an image on the surface 3a of the substrate 3 as a cover member, and / or adjusts the appearance such as glossiness. Each component will be described in detail below.
[0035] <Base material> In this embodiment, the substrate 3 is not particularly limited, but examples thereof include glass and transparent plastic film substrates. The transparent plastic film substrate is not particularly limited, but is preferably one having excellent light transmittance of visible light and excellent transparency (preferably one having a haze value of 5% or less), and examples thereof include the transparent plastic film substrate described in JP-A-2008-90263. As the transparent plastic film substrate, one having optically low birefringence is preferably used. In this embodiment, the substrate 3 can be used as, for example, a cover member of a self-luminous display device, and in this case, the transparent plastic film substrate is preferably a film formed from triacetyl cellulose (TAC), polycarbonate, an acrylic polymer, a polyolefin having a cyclic or norbornene structure, or the like. In addition, in this embodiment, the substrate 3 may be the cover member itself. With such a configuration, a process of laminating a cover member separately can be eliminated in the manufacture of a self-luminous display device, so that the number of processes and necessary members can be reduced, and production efficiency can be improved. Furthermore, with such a configuration, the cover member can be made thinner. When the base material 3 is a cover member, the surface 3a becomes the outermost surface of the self-luminous display device.
[0036] In the optical laminate of the present embodiment, it is preferable that the visible light transmittance T1 of the first adhesive layer 1 and the visible light transmittance T3 of the base material 3 satisfy T1 < T3. This configuration is such that the base material 3 having a higher visible light transmittance than the first adhesive layer 1 is located above the light-emitting element (image display side), which is suitable in that the luminous efficiency can be improved to brighten the image and the power consumption due to the output increase for increasing the emission luminance can be reduced. The visible light transmittance T3 of the base material 3 is not particularly limited, but is, for example, 85 to 100%, and may be 88% or more, 90% or more, or 92% or more.
[0037] In the present embodiment, the thickness of the base material 3 is not particularly limited. However, considering workability such as strength and handleability, and thin layer properties, for example, the range of 10 to 500 μm is preferable, more preferably the range of 20 to 300 μm, and most optimally the range of 30 to 200 μm. The refractive index of the base material 3 is not particularly limited, but is, for example, in the range of 1.30 to 1.80, and preferably in the range of 1.40 to 1.70.
[0038] In the present embodiment, it is preferable that the surface 3a of the base material 3 is subjected to a reflective surface treatment and / or an antiglare treatment 4. When the surface 3a of the base material 3 is subjected to a reflective surface treatment and / or an antiglare treatment 4, the surface 3a becomes the outermost surface of the self-luminous display device, preventing a decrease in visibility due to reflection of external light or reflection of an image, or adjusting the appearance such as glossiness. An antiglare treatment that is easy to manufacture and has a low cost is preferable.
[0039] As the antireflection treatment, a known antireflection treatment can be used without particular limitation, and examples thereof include an antireflection (AR) treatment.
[0040] The anti-reflection (AR) treatment can be applied by any known AR treatment without any particular limitation. Specifically, the AR treatment can be performed by forming an optical thin film with a strictly controlled thickness and refractive index on the surface 3a of the substrate 3, or an anti-reflection layer (AR layer) in which two or more of the optical thin films are laminated. The AR layer exhibits an anti-reflection function by canceling out the inverted phases of incident light and reflected light by utilizing the interference effect of light. The wavelength region of visible light that exhibits the anti-reflection function is, for example, 380 to 780 nm, and the wavelength region with particularly high visibility is 450 to 650 nm, and it is preferable to design the AR layer so as to minimize the reflectance at 550 nm, which is the central wavelength.
[0041] The AR layer generally includes a multi-layer antireflection layer having a structure in which two to five optical thin layers (thin films with strictly controlled thickness and refractive index) are laminated, and by forming multiple layers of components with different refractive indexes to a predetermined thickness, the degree of freedom of the optical design of the AR layer is increased, the antireflection effect can be improved, and the spectral reflection characteristics can be made uniform (flat) in the visible light region. Since high thickness accuracy is required for the optical thin film, generally, each layer is formed by a dry method such as vacuum deposition, sputtering, or CVD.
[0042] The anti-glare (AG) treatment can be any known AG treatment without any particular limitations, and can be performed, for example, by forming an anti-glare layer 4a on the surface 3a of the substrate 3. Any known anti-glare layer can be used without any limitations as the anti-glare layer 4a, and is generally formed as a layer in which inorganic or organic particles are dispersed as an anti-glare agent in a resin.
[0043] In this embodiment, the anti-glare layer 4a is formed using an anti-glare layer forming material containing a resin, particles, and a thixotropy-imparting agent, and the particles and the thixotropy-imparting agent aggregate to form convex portions on the surface of the anti-glare layer 4a. With this configuration, the anti-glare layer 4a has excellent display characteristics that combine anti-glare properties with prevention of white blur, and can prevent the occurrence of protrusions on the surface of the anti-glare layer, which is an appearance defect, and improve product yield, even though the anti-glare layer is formed using particle aggregation.
[0044] Examples of the resin include a thermosetting resin and an ionizing radiation curable resin that is cured by ultraviolet light or light. As the resin, commercially available thermosetting resins and ultraviolet curable resins can also be used.
[0045] As the thermosetting resin or ultraviolet curing resin, for example, a curable compound having at least one of an acrylate group and a methacrylate group that is cured by heat, light (ultraviolet light, etc.), electron beam, etc. can be used, and examples thereof include oligomers or prepolymers of acrylates and methacrylates of polyfunctional compounds such as silicone resins, polyester resins, polyether resins, epoxy resins, urethane resins, alkyd resins, spiroacetal resins, polybutadiene resins, polythiolpolyene resins, polyhydric alcohols, etc. These may be used alone or in combination of two or more types.
[0046] The resin may be, for example, a reactive diluent having at least one of an acrylate group and a methacrylate group. The reactive diluent may be, for example, a reactive diluent described in JP-A-2008-88309, and may include, for example, a monofunctional acrylate, a monofunctional methacrylate, a polyfunctional acrylate, and a polyfunctional methacrylate. The reactive diluent is preferably a trifunctional or higher acrylate or a trifunctional or higher methacrylate. This is because the hardness of the anti-glare layer 4a can be excellent. The reactive diluent may be, for example, butanediol glycerin ether diacrylate, an acrylate of isocyanuric acid, a methacrylate of isocyanuric acid, and the like. These may be used alone or in combination of two or more.
[0047] The particles for forming the anti-glare layer 4a have a main function of making the surface of the anti-glare layer 4a uneven to impart anti-glare properties and to control the haze value of the anti-glare layer 4a. The haze value of the anti-glare layer 4a can be designed by controlling the refractive index difference between the particles and the resin. The particles include, for example, inorganic particles and organic particles. The inorganic particles are not particularly limited, and examples thereof include silicon oxide particles, titanium oxide particles, aluminum oxide particles, zinc oxide particles, tin oxide particles, calcium carbonate particles, barium sulfate particles, talc particles, kaolin particles, calcium sulfate particles, and the like. The organic particles are not particularly limited, and examples thereof include polymethyl methacrylate resin powder (PMMA fine particles), silicone resin powder, polystyrene resin powder, polycarbonate resin powder, acrylic styrene resin powder, benzoguanamine resin powder, melamine resin powder, polyolefin resin powder, polyester resin powder, polyamide resin powder, polyimide resin powder, polyethylene fluoride resin powder, and the like. These inorganic particles and organic particles may be used alone or in combination of two or more kinds.
[0048] The weight average particle diameter (D) of the particles is preferably in the range of 2.5 to 10 μm. By setting the weight average particle diameter of the particles in the above range, for example, anti-glare properties are more excellent and white blur can be prevented. The weight average particle diameter of the particles is more preferably in the range of 3 to 7 μm. The weight average particle diameter of the particles can be measured, for example, by the Coulter counting method. For example, a particle size distribution measuring device using a pore electrical resistance method (product name: Coulter Multisizer, manufactured by Beckman Coulter, Inc.) is used to measure the number and volume of the particles by measuring the electrical resistance of an electrolyte solution equivalent to the volume of the particles when the particles pass through the pores, and the weight average particle diameter is calculated.
[0049] The shape of the particles is not particularly limited, and may be, for example, roughly spherical like beads, or irregularly shaped like powder, but roughly spherical particles are preferred, more preferably roughly spherical particles with an aspect ratio of 1.5 or less, and most preferably spherical particles.
[0050] The ratio of the particles in the anti-glare layer 4a is preferably in the range of 0.2 to 12 parts by weight, more preferably in the range of 0.5 to 12 parts by weight, and even more preferably in the range of 1 to 7 parts by weight, relative to 100 parts by weight of the resin. By setting the ratio in this range, for example, the anti-glare property is more excellent and white blur can be prevented.
[0051] Examples of the thixotropy-imparting agent for forming the anti-glare layer 4a include organic clay, oxidized polyolefin, and modified urea.
[0052] The organoclay is preferably a clay that has been subjected to an organo-treatment in order to improve the affinity with the resin. For example, the organoclay may be a layered organoclay. The organoclay may be prepared at home or may be a commercially available product. Examples of the commercially available products include Lucentite SAN, Lucentite STN, Lucentite SEN, Lucentite SPN, Somasif ME-100, Somasif MAE, Somasif MTE, Somasif MEE, and Somasif MPE (trade names, all manufactured by Co-op Chemical Co., Ltd.); Esben, Esben C, Esben E, Esben W, Esben P, Esben WX, Esben N-400, Esben NX, Esben NX80, Esben NO12S, Esben NEZ, Esben NO12, Esben NE, Esben NZ, Esben NZ70, Organite, Organite D, and Organite T (trade names, all manufactured by Hojun Co., Ltd.); Kunipia F, Kunipia G, and Kunipia G4 (trade names, all manufactured by Kunimine Kogyo Co., Ltd.); Thixogel VZ, Clayton HT, and Clayton 40 (trade names, all manufactured by Rockwood Additives Co., Ltd.).
[0053] The oxidized polyolefin may be prepared in-house or may be a commercially available product, such as Disparlon 4200-20 (trade name, manufactured by Kusumoto Chemical Industries, Ltd.) or Flonone SA300 (trade name, manufactured by Kyoeisha Chemical Industries, Ltd.).
[0054] The modified urea is a reaction product of an isocyanate monomer or its adduct with an organic amine. The modified urea may be prepared in-house or may be a commercially available product. Examples of the commercially available product include BYK410 (manufactured by BYK-Chemie).
[0055] The thixotropy-imparting agents may be used alone or in combination of two or more kinds.
[0056] In this embodiment, the height of the convex portion from the roughness mean line of the anti-glare layer 4a is preferably less than 0.4 times the thickness of the anti-glare layer 4a. More preferably, it is in the range of 0.01 times or more and less than 0.4 times, and even more preferably, it is in the range of 0.01 times or more and less than 0.3 times. Within this range, it is possible to suitably prevent the formation of protrusions that become appearance defects on the convex portion. The anti-glare layer 4a of this embodiment can be made less likely to cause appearance defects by having convex portions of such height. Here, the height from the mean line can be measured, for example, by the method described in JP 2017-138620 A.
[0057] The ratio of the thixotropy-imparting agent in the anti-glare layer 4a is preferably in the range of 0.1 to 5 parts by weight, and more preferably in the range of 0.2 to 4 parts by weight, relative to 100 parts by weight of the resin.
[0058] The thickness (d) of the antiglare layer 4a is not particularly limited, but is preferably within the range of 3 to 12 μm. By setting the thickness (d) of the antiglare layer 4a within the above range, for example, curling of the optical laminate 12 can be prevented, and problems such as poor transportability and other reduced productivity can be avoided. In addition, when the thickness (d) is within the above range, the weight average particle size (D) of the particles is preferably within the range of 2.5 to 10 μm, as described above. By combining the thickness (d) of the antiglare layer 4a and the weight average particle size (D) of the particles as described above, the antiglare layer 4a can have even better antiglare properties. The thickness (d) of the antiglare layer 4a is more preferably within the range of 3 to 8 μm.
[0059] The relationship between the thickness (d) of the anti-glare layer 4a and the weight average particle size (D) of the particles is preferably within the range of 0.3≦D / d≦0.9. This relationship makes it possible to provide an anti-glare layer with better anti-glare properties, prevention of white blur, and no defects in appearance.
[0060] In the optical laminate 12 of this embodiment, as described above, the anti-glare layer 4a forms a convex portion on the surface of the anti-glare layer 4a by agglomeration of the particles and the thixotropy-imparting agent. In the aggregated portion forming the convex portion, the particles are present in a state of being gathered in a plurality of particles in the surface direction of the anti-glare layer 4a. As a result, the convex portion has a gentle shape. By having a convex portion of such a shape, the anti-glare layer 4a of this embodiment can maintain anti-glare properties and prevent white blurring, and further, can make it difficult for appearance defects to occur.
[0061] The surface shape of the anti-glare layer 4a can be designed arbitrarily by controlling the aggregation state of the particles contained in the anti-glare layer-forming material. The aggregation state of the particles can be controlled, for example, by the material of the particles (for example, the chemical modification state of the particle surface, affinity to the solvent or resin, etc.), the type and combination of the resin (binder) or solvent, etc. Here, in this embodiment, the aggregation state of the particles can be controlled by the thixotropy-imparting agent contained in the anti-glare layer-forming material. As a result, in this embodiment, the aggregation state of the particles can be made as described above, and the convex portion can be made into a gentle shape.
[0062] In the optical laminate 12 of this embodiment, when the base material 3 is made of a resin or the like, it is preferable that the base material 3 and the anti-glare layer 4a have a permeation layer at the interface between the base material 3 and the anti-glare layer 4a. The permeation layer is formed by the resin component contained in the material for forming the anti-glare layer 4a permeating into the base material 3. When the permeation layer is formed, the adhesion between the base material 3 and the anti-glare layer 4a can be improved, which is preferable. The permeation layer preferably has a thickness in the range of 0.2 to 3 μm, more preferably in the range of 0.5 to 2 μm. For example, when the base material 3 is triacetyl cellulose and the resin contained in the anti-glare layer 4a is an acrylic resin, the permeation layer can be formed. The permeation layer can be confirmed, for example, by observing the cross section of the optical laminate 12 with a transmission electron microscope (TEM), and the thickness can be measured.
[0063] In this embodiment, even when the optical laminate 12 having such a permeation layer is applied, it is possible to easily form a desired smooth surface unevenness that achieves both anti-glare properties and prevention of white blur. The permeation layer is preferably formed thicker for a substrate 3 having poor adhesion to the anti-glare layer 4a in order to improve adhesion.
[0064] In this embodiment, in the anti-glare layer 4a, the appearance defect having a maximum diameter of 200 μm or more is within 1 mm of the anti-glare layer 4a. 2 It is preferable that the number of defects in appearance is one or less per one. It is more preferable that the number of defects in appearance is zero.
[0065] In this embodiment, the substrate 3 on which the anti-glare layer 4a is formed preferably has a haze value in the range of 0 to 10%. The haze value is a haze value (cloudiness) according to JIS K 7136 (2000 edition). The haze value is more preferably in the range of 0 to 5%, and even more preferably in the range of 0 to 3%. In order to set the haze value in the above range, it is preferable to select the particles and the resin so that the refractive index difference between the particles and the resin is in the range of 0.001 to 0.02. By setting the haze value in the above range, a clear image can be obtained and the contrast in a dark place can be improved.
[0066] In this embodiment, in the uneven shape of the surface of the anti-glare layer 4a, the average tilt angle θa (°) is preferably in the range of 0.1 to 5.0, more preferably in the range of 0.3 to 4.5, even more preferably in the range of 1.0 to 4.0, and particularly preferably in the range of 1.6 to 4.0. Here, the average tilt angle θa is a value defined by the following mathematical formula (1). The average tilt angle θa is a value measured, for example, by the method described in JP 2017-138620 A. Average inclination angle θa=tan-1Δa (1)
[0067] In the above formula (1), Δa is the value obtained by dividing the sum (h1+h2+h3···+hn) of the differences (heights h) between the peaks of adjacent peaks and the lowest points of adjacent valleys in the reference length L of a roughness curve defined in JIS B 0601 (1994 edition) as shown in the following formula (2). The roughness curve is a curve obtained by removing surface waviness components longer than a predetermined wavelength from a profile curve using a phase difference compensation high-pass filter. The profile curve is the outline that appears at the cut surface when the target surface is cut by a plane perpendicular to the target surface. Δa = (h1 + h2 + h3 + hn) / L (2)
[0068] When θa is in the above range, the anti-glare property is more excellent and white blur can be prevented.
[0069] When forming the anti-glare layer 4a, it is preferable that the prepared anti-glare layer forming material (coating liquid) exhibits thixotropy, and the Ti value defined below is preferably in the range of 1.3 to 3.5, and more preferably in the range of 1.3 to 2.8. Ti value = β1 / β2 Here, β1 is the viscosity measured using a Rheostress 6000 manufactured by HAAKE at a shear rate of 20 (1 / s), and β2 is the viscosity measured using a Rheostress 6000 manufactured by HAAKE at a shear rate of 200 (1 / s).
[0070] If the Ti value is less than 1.3, defects in appearance are likely to occur, and anti-glare properties and white blur properties are deteriorated, whereas if the Ti value exceeds 3.5, the particles are unlikely to aggregate and are likely to be in a dispersed state.
[0071] The method for producing the anti-glare layer 4a of this embodiment is not particularly limited and may be any method, but for example, the anti-glare layer can be produced by preparing an anti-glare layer forming material (coating liquid) containing the resin, the particles, the thixotropy-imparting agent, and a solvent, applying the anti-glare layer forming material (coating liquid) to the surface 3a of the substrate 3 to form a coating film, and curing the coating film to form the anti-glare layer 4a. In this embodiment, a method of imparting a concave-convex shape by a transfer method using a mold, sandblasting, an embossing roll, or other appropriate method may also be used.
[0072] The solvent is not particularly limited, and various solvents can be used, and one type may be used alone, or two or more types may be used in combination. There are optimal solvent types and solvent ratios depending on the composition of the resin, the type and content of the particles and the thixotropy-imparting agent, etc. The solvent is not particularly limited, and examples thereof include alcohols such as methanol, ethanol, isopropyl alcohol, butanol, and 2-methoxyethanol; ketones such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclopentanone; esters such as methyl acetate, ethyl acetate, and butyl acetate; ethers such as diisopropyl ether and propylene glycol monomethyl ether; glycols such as ethylene glycol and propylene glycol; cellosolves such as ethyl cellosolve and butyl cellosolve; aliphatic hydrocarbons such as hexane, heptane, and octane; and aromatic hydrocarbons such as benzene, toluene, and xylene.
[0073] When the permeation layer is formed by using, for example, triacetyl cellulose (TAC) as the base material 3, a good solvent for TAC can be suitably used. Examples of the solvent include ethyl acetate, methyl ethyl ketone, and cyclopentanone.
[0074] In addition, by appropriately selecting the solvent, the thixotropy of the anti-glare layer forming material (coating liquid) can be well expressed by the thixotropy imparting agent.For example, when using organic clay, toluene and xylene can be preferably used alone or in combination; for example, when using oxidized polyolefin, methyl ethyl ketone, ethyl acetate, propylene glycol monomethyl ether can be preferably used alone or in combination; for example, when using modified urea, butyl acetate and methyl isobutyl ketone can be preferably used alone or in combination.
[0075] Various leveling agents can be added to the anti-glare layer forming material. As the leveling agent, for example, a fluorine-based or silicone-based leveling agent can be used for the purpose of preventing coating unevenness (uniformity of the coating surface). In this embodiment, a leveling agent can be appropriately selected depending on the case where antifouling is required on the surface of the anti-glare layer 4a, or the case where an antireflection layer (low refractive index layer) or a layer containing an interlayer filler is formed on the anti-glare layer 4a. In this embodiment, for example, the thixotropy-imparting agent can be included to cause the coating liquid to exhibit thixotropy, so that coating unevenness is unlikely to occur. Therefore, this embodiment has an advantage that, for example, the selection of the leveling agent can be expanded.
[0076] The amount of the leveling agent added is, for example, 5 parts by weight or less, and preferably in the range of 0.01 to 5 parts by weight, relative to 100 parts by weight of the resin.
[0077] The anti-glare layer-forming material may contain, as necessary, pigments, fillers, dispersants, plasticizers, UV absorbers, surfactants, antifouling agents, antioxidants, etc., within the scope of not impairing the performance. These additives may be used alone or in combination of two or more.
[0078] For the anti-glare layer forming material, a conventionally known photopolymerization initiator such as that described in JP-A-2008-88309 can be used.
[0079] The anti-glare layer forming material can be applied to the surface 3a of the substrate 3 by a coating method such as fountain coating, die coating, spin coating, spray coating, gravure coating, roll coating, or bar coating.
[0080] The anti-glare layer-forming material is applied to the substrate 3 to form a coating film, and the coating film is cured. Prior to the curing, it is preferable to dry the coating film. The drying may be, for example, natural drying, air drying by blowing air, heat drying, or a combination of these methods.
[0081] The means for curing the coating film of the anti-glare layer-forming material is not particularly limited, but ultraviolet curing is preferred. The irradiation dose of the energy ray source is 50 to 500 mJ / cm2 as the cumulative exposure dose at an ultraviolet wavelength of 365 nm. 2 The irradiation dose is preferably 50 mJ / cm. 2 If the curing rate is 500 mJ / cm or more, the curing is more sufficient, and the hardness of the formed anti-glare layer is more sufficient. 2 If the content is equal to or less than this, coloring of the formed anti-glare layer can be prevented.
[0082] In this manner, the anti-glare layer 4a can be formed on the surface 3a of the substrate 3. The anti-glare layer 4a may be formed by a manufacturing method other than the above-mentioned method. The hardness of the anti-glare layer 4a of this embodiment is preferably a pencil hardness of 2H or more, although it is also affected by the thickness of the layer.
[0083] In this embodiment, the anti-glare layer 4a may have a multi-layer structure in which two or more layers are laminated.
[0084] In this embodiment, the above-mentioned AR layer (low refractive index layer) may be disposed on the anti-glare layer 4a. For example, when the optical laminate 12 according to this embodiment is mounted on a self-luminous display device, one of the factors that reduces the visibility of an image is the reflection of light at the interface between air and the anti-glare layer. The AR layer reduces the surface reflection. The anti-glare layer 3a and the anti-reflection layer may each have a multi-layer structure in which two or more layers are laminated.
[0085] In order to prevent adhesion of contaminants and to improve the ease of removal of adhered contaminants, it is preferable to laminate a contamination prevention layer formed from a fluorine group-containing silane compound or a fluorine group-containing organic compound on the anti-glare layer 4a.
[0086] In this embodiment, it is preferable to perform a surface treatment on at least one of the substrate 3 and the anti-glare layer 4a. By performing a surface treatment on the substrate 3, the adhesion to the anti-glare layer 4a is further improved. In addition, by performing a surface treatment on the anti-glare layer 4a, the adhesion to the AR layer is further improved.
[0087] A solvent treatment may be performed on the other surface of the anti-glare layer 4a in order to prevent curling of the substrate 3. Also, in order to prevent curling, a transparent resin layer may be formed on the other surface of the anti-glare layer 4a.
[0088] <Adhesive layer> In this embodiment, the first pressure-sensitive adhesive layer 1 and the second pressure-sensitive adhesive layer 2 are pressure-sensitive adhesive layers formed from a pressure-sensitive adhesive composition selected from a photocurable pressure-sensitive adhesive composition and a solvent-based pressure-sensitive adhesive composition.
[0089] In this embodiment, the first adhesive layer 1 and the second adhesive layer 2 may both be adhesive layers formed from a photocurable adhesive composition, or both may be adhesive layers formed from a solvent-based adhesive composition, or one may be an adhesive layer formed from a photocurable adhesive composition and the other an adhesive layer formed from a solvent-based adhesive composition.
[0090] In this embodiment, the first adhesive layer 1 is preferably an adhesive layer formed from a solvent-based adhesive composition in that it is excellent in step absorption and also in workability. On the other hand, the second adhesive layer 2 may be an adhesive layer formed from a photocurable adhesive composition or an adhesive layer formed from a solvent-based adhesive composition.
[0091] The adhesive composition forming the first adhesive layer 1 preferably contains a colorant. When the adhesive composition forming the first adhesive layer 1 contains a colorant, the transmittance of the first adhesive layer 1 to visible light decreases, which is preferable for the configuration where T1 and T2 satisfy T1 < T2. The first adhesive layer 1 with reduced transmittance to visible light and imparted light-shielding property seals the space between the metal wiring layer 6 and the LED chip of the self-luminous display device (mini / micro LED display device) of the present embodiment, thereby preventing reflection by metal wiring or the like, preventing color mixing between LED chips, and improving the contrast of the image.
[0092] The adhesive composition forming the second adhesive layer 2 may contain a colorant, but from the viewpoint of the configuration where T1 and T2 satisfy T1 < T2, it is preferably free of a colorant.
[0093] <Photocurable Adhesive Composition> The photocurable adhesive composition contains a polymer, a photopolymerizable compound, and a photoinitiator. That is, the photocurable adhesive composition used for forming the first adhesive layer 1 and the second adhesive layer 2 of the present embodiment contains a polymer, a photopolymerizable compound, and a photoinitiator.
[0094] The adhesive layer formed using the photocurable adhesive composition is roughly classified into a type that performs photocuring (first form) and a type that does not perform photocuring but performs photocuring after being bonded to a display panel described later (second form). The first adhesive layer 1 and the second adhesive layer 2 may both be adhesive layers of the first form, may both be adhesive layers of the second form, or one may be an adhesive layer of the first form and the other may be an adhesive layer of the second form.
[0095] [First form] The pressure-sensitive adhesive layer of the first embodiment can be formed by applying a photocurable pressure-sensitive adhesive composition containing a polymer, a photopolymerizable compound, and a photopolymerization initiator onto a release film, and then photocuring the composition.
[0096] <Photocurable adhesive composition> (polymer) Examples of the polymer contained in the photocurable pressure-sensitive adhesive composition include acrylic polymers, silicone polymers, polyesters, polyurethanes, polyamides, polyvinyl ethers, vinyl acetate / vinyl chloride copolymers, modified polyolefins, epoxy-based, fluorine-based, and rubber-based polymers such as natural rubber and synthetic rubber. In particular, acrylic polymers are preferably used because they exhibit appropriate adhesive properties such as wettability, cohesiveness, and adhesiveness, and are also excellent in weather resistance and heat resistance.
[0097] The acrylic polymer contains a (meth)acrylic acid alkyl ester as a main constituent monomer component. In this specification, "(meth)acrylic" means acrylic and / or methacrylic. The amount of the (meth)acrylic acid alkyl ester relative to the total amount of the monomer components constituting the acrylic polymer is preferably 50% by weight or more, more preferably 55% by weight or more, and even more preferably 60% by weight or more.
[0098] The (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl group with a carbon number of 1 to 20. The (meth)acrylic acid alkyl ester may have a branched alkyl group or may have a cyclic alkyl group.
[0099] Specific examples of (meth)acrylic acid alkyl esters having a chain alkyl group include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, and isooctyl (meth)acrylate. Examples of the (meth)acrylate alkyl ester having a chain alkyl group that is preferred for use in the first embodiment include butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octadecyl (meth)acrylate, and dodecyl (meth)acrylate. The amount of the (meth)acrylic acid alkyl ester having a chain alkyl group relative to the total amount of monomer components constituting the acrylic polymer is, for example, about 40 to 90% by weight, and may be 45 to 80% by weight, or 50 to 70% by weight.
[0100] Specific examples of the (meth)acrylic acid alkyl ester having an alicyclic alkyl group include (meth)acrylic acid cycloalkyl esters such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, and cyclooctyl (meth)acrylate; (meth)acrylic acid esters having a bicyclic aliphatic hydrocarbon ring such as isobornyl (meth)acrylate; and (meth)acrylic acid esters having a tricyclic or higher aliphatic hydrocarbon ring such as dicyclopentanyl (meth)acrylate, dicyclopentanyloxyethyl (meth)acrylate, tricyclopentanyl (meth)acrylate, 1-adamantyl (meth)acrylate, 2-methyl-2-adamantyl (meth)acrylate, and 2-ethyl-2-adamantyl (meth)acrylate. Preferred (meth)acrylic acid alkyl esters having an alicyclic alkyl group used in the first embodiment include cyclohexyl (meth)acrylate and isobornyl (meth)acrylate. The amount of the (meth)acrylic acid alkyl ester having an alicyclic alkyl group relative to the total amount of monomer components constituting the acrylic polymer is, for example, about 3 to 50% by weight, and may be 5 to 40% by weight or 10 to 30% by weight.
[0101] The acrylic polymer may contain a polar group-containing monomer such as a hydroxyl group-containing monomer, a carboxyl group-containing monomer, or a nitrogen-containing monomer as a constituent monomer component. When the acrylic polymer contains a polar group-containing monomer as a constituent monomer component, the cohesive strength of the adhesive tends to be increased and the adhesive strength tends to be improved. Preferred polar group-containing monomers used in the first embodiment are hydroxyl group-containing monomers and nitrogen-containing monomers. The amount of the polar group-containing monomer (the total of the hydroxyl group-containing monomer, the carboxyl group-containing monomer, and the nitrogen-containing monomer) relative to the total amount of the monomer components constituting the acrylic polymer is, for example, about 3 to 50% by weight, and may be 5 to 40% by weight or 10 to 30% by weight.
[0102] Examples of the hydroxyl group-containing monomer include (meth)acrylic acid esters such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)-methyl (meth)acrylate. When a crosslinking structure is introduced into the polymer by an isocyanate crosslinking agent, the hydroxyl group can be a reaction point (crosslinking point) with the isocyanate group. Preferred hydroxyl group-containing monomers used in the first embodiment are 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate. The amount of the hydroxyl group-containing monomer relative to the total amount of monomer components constituting the acrylic polymer is, for example, about 3 to 50% by weight, and may be 5 to 40% by weight or 10 to 30% by weight.
[0103] Examples of the carboxyl group-containing monomer include acrylic monomers such as (meth)acrylic acid, carboxyethyl (meth)acrylate, and carboxypentyl (meth)acrylate, as well as itaconic acid, maleic acid, fumaric acid, and crotonic acid. When a crosslinking structure is introduced into the polymer by an epoxy crosslinking agent, the carboxyl group can be a reaction point (crosslinking point) with the epoxy group. A preferred carboxyl group-containing monomer used in the first embodiment is (meth)acrylic acid. The amount of the carboxyl group-containing monomer relative to the total amount of monomer components constituting the acrylic polymer is, for example, about 3 to 50% by weight, and may be 5 to 40% by weight, or 10 to 30% by weight.
[0104] Examples of the nitrogen-containing monomer include vinyl monomers such as N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, (meth)acryloylmorpholine, N-vinylcarboxylic acid amides, N-vinylcaprolactam, and acrylamide, and cyano group-containing monomers such as acrylonitrile and methacrylonitrile. A preferred nitrogen-containing monomer used in the first embodiment is N-vinylpyrrolidone. The amount of the nitrogen-containing monomer relative to the total amount of monomer components constituting the acrylic polymer is, for example, about 3 to 50% by weight, and may be 5 to 40% by weight or 10 to 30% by weight.
[0105] The acrylic polymer may contain, as monomer components other than those mentioned above (sometimes referred to as "other monomers"), vinyl monomers such as acid anhydride group-containing monomers, caprolactone adducts of (meth)acrylic acid, sulfonic acid group-containing monomers, phosphoric acid group-containing monomers, vinyl acetate, vinyl propionate, styrene, and α-methylstyrene; epoxy group-containing monomers such as glycidyl (meth)acrylate; glycol-based acrylic ester monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; and acrylic ester monomers such as tetrahydrofurfuryl (meth)acrylate, fluorine (meth)acrylate, silicone (meth)acrylate, and 2-methoxyethyl (meth)acrylate.
[0106] The glass transition temperature (Tg) of the polymer contained in the photocurable pressure-sensitive adhesive composition is preferably 0°C or lower. The glass transition temperature of the polymer may be -5°C or lower, -10°C or lower, or -15°C or lower. The glass transition temperature of the polymer is the peak top temperature of the loss tangent (tan δ) measured by dynamic viscoelasticity measurement. When a crosslinked structure is introduced into the polymer, the glass transition temperature may be calculated based on the theoretical Tg from the composition of the polymer. The theoretical Tg is calculated by the Fox formula described below.
[0107] The above monomer components are polymerized by various known methods to obtain a polymer. The polymerization method is not particularly limited, but it is preferable to prepare the polymer by photopolymerization. Since the polymer can be prepared without using a solvent in photopolymerization, it is not necessary to dry and remove the solvent when forming the pressure-sensitive adhesive layer, and a pressure-sensitive adhesive layer with a large thickness can be formed uniformly.
[0108] In the preparation of the first type of pressure-sensitive adhesive layer, it is preferable to prepare a polymer (prepolymer) with a low degree of polymerization in which a part of the monomer component remains unreacted. The composition (prepolymer forming composition) used for preparing the prepolymer preferably contains a photopolymerization initiator in addition to the monomer. The photopolymerization initiator may be appropriately selected according to the type of monomer. For example, a photoradical polymerization initiator is used for polymerization of an acrylic polymer. Examples of the photopolymerization initiator include a benzoin ether-based photopolymerization initiator, an acetophenone-based photopolymerization initiator, an α-ketol-based photopolymerization initiator, an aromatic sulfonyl chloride-based photopolymerization initiator, a photoactive oxime-based photopolymerization initiator, a benzoin-based photopolymerization initiator, a benzyl-based photopolymerization initiator, a benzophenone-based photopolymerization initiator, a ketal-based photopolymerization initiator, a thioxanthone-based photopolymerization initiator, and an acylphosphine oxide-based photopolymerization initiator.
[0109] In the polymerization, a chain transfer agent, a polymerization inhibitor (polymerization retarder), etc. may be used for the purpose of molecular weight adjustment, etc. Examples of the chain transfer agent include thiols such as α-thioglycerol, lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, and 2,3-dimercapto-1-propanol, and α-methylstyrene dimer.
[0110] The polymerization rate of the prepolymer is not particularly limited, but is preferably 3 to 50% by weight, more preferably 5 to 40% by weight, from the viewpoint of obtaining a viscosity suitable for application onto a substrate. The polymerization rate of the prepolymer can be adjusted to a desired range by adjusting the type and amount of photopolymerization initiator, the irradiation intensity and irradiation time of active light such as UV light, etc. The polymerization rate of the prepolymer is the non-volatile content when heated at 130°C for 3 hours, and is calculated by the following formula. The polymerization rate (non-volatile content) of the pressure-sensitive adhesive layer is also measured by the same method. Polymerization rate (%) = weight after heating / weight before heating x 100
[0111] As described above, the photocurable adhesive composition used to form the adhesive layer contains a polymer, a photopolymerizable compound, and a photopolymerization initiator. For example, the photocurable adhesive composition can be obtained by adding the photopolymerizable compound and the photopolymerization initiator to a prepolymer. Instead of using a prepolymer, a low molecular weight polymer (oligomer) can be used, and the low molecular weight polymer can be mixed with the photopolymerizable compound, the photopolymerization initiator, and a colorant to prepare the photocurable adhesive composition.
[0112] (Photopolymerizable compound) The photopolymerizable compound contained in the photocurable pressure-sensitive adhesive composition has one or more photopolymerizable functional groups in one molecule. The photopolymerizable functional group may be any of radical polymerizable, cationic polymerizable, and anionic polymerizable, but a radical polymerizable functional group having an unsaturated double bond (ethylenically unsaturated group) is preferred because of its excellent reactivity.
[0113] The prepolymer contains a monomer that has not reacted with the polymer, and the unreacted monomer retains photopolymerizability. Therefore, in the preparation of the photocurable pressure-sensitive adhesive composition, it is not necessary to add a photopolymerizable compound. When a photopolymerizable compound is added to the prepolymer, the photopolymerizable compound to be added may be the same as or different from the monomer used in the preparation of the prepolymer.
[0114] When the polymer is an acrylic polymer, the compound added as the photopolymerizable compound is preferably a monomer or oligomer having a (meth)acryloyl group as a photopolymerizable functional group, since it has high compatibility with the polymer. The photopolymerizable compound may be a polyfunctional compound having two or more photopolymerizable functional groups in one molecule. Examples of the photopolymerizable polyfunctional compound include polyfunctional (meth)acrylates. Examples of the polyfunctional (meth)acrylates include bifunctional compounds such as polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, bisphenol A ethylene oxide modified di(meth)acrylate, bisphenol A propylene oxide modified di(meth)acrylate, alkanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, pentaerythritol di(meth)acrylate, neopentyl glycol di(meth)acrylate, glycerin di(meth)acrylate, and urethane di(meth)acrylate. functional (meth)acrylic acid esters; trifunctional (meth)acrylic acid esters such as pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, and ethoxylated isocyanuric acid tri(meth)acrylate; tetrafunctional (meth)acrylic acid esters such as ditrimethylolpropane tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and penta- or higher functional (meth)acrylic acid esters such as dipentaerythritol penta(meth)acrylate and dipentaerythritol hexa(meth)acrylate.
[0115] When a polyfunctional compound is used as the photopolymerizable compound, the amount of the polyfunctional compound used is preferably 10 parts by weight or less, more preferably 0.001 to 1 part by weight, and even more preferably 0.005 to 0.5 parts by weight, relative to 100 parts by weight of the polymer (including the prepolymer). If the amount of the polyfunctional monomer used is excessively large, the adhesive layer after photocuring may have low viscosity and poor adhesive strength. The amount of the polyfunctional compound used may be 10 parts by weight or less, 5 parts by weight or less, 3 parts by weight or less, or 1 part by weight or less. The amount of the polyfunctional monomer used may be 0, 0.001 parts by weight or more, 0.01 parts by weight or more, or 0.1 parts by weight or more.
[0116] When a monomer forming a prepolymer is used as the photopolymerizable compound, a hydroxyl group-containing monomer is preferred, and 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are more preferred. When a hydroxyl group-containing monomer is used as the photopolymerizable compound, the amount of the hydroxyl group-containing monomer used is preferably 40 parts by weight or less, more preferably 1 to 30 parts by weight, and even more preferably 5 to 20 parts by weight, relative to 100 parts by weight of the polymer (including the prepolymer). The amount of the hydroxyl group-containing monomer used may be 40 parts by weight or less, 30 parts by weight or less, or 20 parts by weight or less. The amount of the hydroxyl group-containing monomer used may be 0, 1 part by weight or more, 5 parts by weight or more, or 10 parts by weight or more.
[0117] (Photopolymerization initiator) The photocurable adhesive composition contains a photopolymerization initiator. The photopolymerization initiator generates radicals, acids, bases, etc., when irradiated with active light such as ultraviolet light, and can be appropriately selected depending on the type of photopolymerizable compound, etc. When the photopolymerizable compound is a compound having a (meth)acryloyl group (e.g., monofunctional or polyfunctional (meth)acrylate), it is preferable to use a photoradical polymerization initiator as the photopolymerization initiator. The photopolymerization initiator may be used alone or in a mixture of two or more kinds.
[0118] When the photoinitiator used in the preparation (polymerization) of the polymer (including prepolymer) remains without deactivation, the addition of the photoinitiator may be omitted. When adding a photoinitiator to the polymer, the photoinitiator to be added may be the same as or different from the photoinitiator used in the preparation of the polymer.
[0119] The photoinitiator contained in the photocurable pressure-sensitive adhesive composition preferably has an absorption maximum in a wavelength region where the light absorption by the colorant described below is small. Specifically, the photoinitiator preferably has an absorption maximum in the wavelength region of 330 to 400 nm. Since the photoinitiator has an absorption maximum in a region where the light absorption by the colorant is small, the curing inhibition by the colorant is suppressed, and the polymerization rate can be sufficiently increased by photocuring. Examples of the photo radical polymerization initiator having an absorption maximum in the wavelength region of 330 to 400 nm include hydroxyketones, benzyldimethylketals, aminoketones, acylphosphine oxides, benzophenones, and triazine derivatives containing a trichloromethyl group.
[0120] The content of the photoinitiator in the photocurable pressure-sensitive adhesive composition is about 0.01 to 10 parts by weight, preferably about 0.05 to 5 parts by weight, based on 100 parts by weight of the total amount of monomers (monomers used in the preparation of the polymer and photopolymerizable compounds added to the polymer).
[0121] (Colorant) The photocurable pressure-sensitive adhesive composition used in the first form may contain a colorant. In particular, it is preferable that the photocurable pressure-sensitive adhesive composition forming the first adhesive layer 1 further contains a colorant. When the photocurable pressure-sensitive adhesive composition forming the first adhesive layer 1 contains a colorant, the transmittance of the first adhesive layer 1 to visible light decreases, which is preferable for the configuration in which T1 and T2 satisfy T1 < T2. By sealing the space between the metal wiring layer 6 and the LED chip of the self-luminous display device (mini / micro LED display device) of the present embodiment with the first adhesive layer 1 having reduced transmittance to visible light and imparted light-shielding properties, reflection by the metal wiring or the like is prevented, color mixing between the LED chips is prevented, and the contrast of the image is improved.
[0122] The colorant may be a dye or a pigment as long as it is soluble or dispersible in the photocurable adhesive composition. Dyes are preferred because they can achieve low haze even with a small amount of addition, and are easy to distribute uniformly without sedimentation like pigments. Pigments are also preferred because they have high color expression even with a small amount of addition. When using a pigment as a colorant, it is preferable that the pigment has low or no electrical conductivity. When using a dye, it is preferable to use it in combination with an antioxidant, which will be described later.
[0123] The colorant is not particularly limited, but is preferably one that absorbs visible light and transmits ultraviolet light. That is, it is preferable that the colorant has an average transmittance at wavelengths of 330 to 400 nm greater than that at wavelengths of 400 to 700 nm. The transmittance of the colorant is measured using a solution or dispersion diluted with an appropriate solvent or dispersion medium (an organic solvent with low absorption in the wavelength range of 330 to 700 nm) such as tetrahydrofuran (THF) so that the transmittance at a wavelength of 400 nm is about 50 to 60%.
[0124] Examples of ultraviolet-transmitting black pigments that absorb less ultraviolet light than visible light include "9050BLACK" and "UVBK-0001" manufactured by Tokushiki Co., Ltd. Examples of ultraviolet-transmitting black dyes include "SOC-L-0123" manufactured by Orient Chemical Industries Co., Ltd.
[0125] Carbon black and titanium black, which are generally used as black colorants, have a higher ultraviolet absorption than visible light absorption (UV transmittance is lower than visible light transmittance). Therefore, when a colorant such as carbon black is added to a photocurable adhesive composition sensitive to ultraviolet light, most of the ultraviolet light irradiated for photocuring is absorbed by the colorant, the amount of light absorbed by the photopolymerization initiator is small, and photocuring takes time (the cumulative amount of light irradiation increases). In addition, when the thickness of the adhesive layer is large, there is little ultraviolet light reaching the surface opposite to the light irradiated surface, so that even if light is irradiated for a long time, photocuring tends to be insufficient. In contrast, by using a colorant with a higher ultraviolet transmittance than visible light, it is possible to suppress the curing inhibition caused by the colorant.
[0126] The content of the colorant in the photocurable adhesive composition forming the first adhesive layer is, for example, about 0.01 to 20 parts by weight relative to 100 parts by weight of the total amount of monomers, and may be appropriately set depending on the type of colorant, the color tone and light transmittance of the adhesive layer, etc. The colorant may be added to the composition as a solution or dispersion in which it is dissolved or dispersed in an appropriate solvent.
[0127] The photocurable adhesive composition forming the second adhesive layer preferably does not contain a colorant. The photocurable adhesive composition forming the second adhesive layer does not contain a colorant, so that the transmittance to visible light is increased, and the luminous efficiency of the self-luminous display device (mini / micro LED display device) is improved. When the photocurable adhesive composition forming the second adhesive layer contains a colorant, the content is, for example, about 0.1 parts by weight or less with respect to 100 parts by weight of the total amount of monomers. Even if the photocurable adhesive composition forming the second adhesive layer does not contain a colorant, the colorant contained in the first adhesive layer may migrate to the second adhesive layer.
[0128] (Silane coupling agent) The photocurable adhesive composition may contain a silane coupling agent within a range that does not impair the effects of the present invention. When the photocurable adhesive composition contains a silane coupling agent, the adhesive reliability to glass (particularly, the adhesive reliability to glass under a high temperature and high humidity environment) is improved, which is preferable.
[0129] The silane coupling agent is not particularly limited, but preferably includes γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-phenyl-aminopropyltrimethoxysilane, 3-acryloxypropyltrimethoxysilane, etc. Among them, γ-glycidoxypropyltrimethoxysilane is preferable. In addition, as a commercially available product, for example, the product name "KBM-403" (manufactured by Shin-Etsu Chemical Co., Ltd.) can be mentioned. The silane coupling agent may be used alone or in combination of two or more kinds.
[0130] The content of the silane coupling agent in the photocurable pressure-sensitive adhesive composition is not particularly limited, but is preferably 0.01 to 1 part by weight, and more preferably 0.03 to 0.5 parts by weight, based on 100 parts by weight of the polymer.
[0131] (Other Ingredients) In the first embodiment, the photocurable adhesive composition may contain components other than the polymer, the photopolymerizable compound, the photopolymerization initiator, and the colorant. For example, a chain transfer agent may be contained for the purpose of adjusting the photocuring speed. In addition, an oligomer or a tackifier may be contained for the purpose of adjusting the viscosity of the photocurable adhesive composition or adjusting the adhesive strength of the adhesive layer. As the oligomer, for example, one having a weight average molecular weight of about 1000 to 30000 is used. As the oligomer, an acrylic oligomer is preferable because it has excellent compatibility with acrylic polymers. The photocurable adhesive composition may contain additives such as a plasticizer, a softener, an antidegradant, a filler, an antioxidant, a surfactant, and an antistatic agent.
[0132] [Second form] The pressure-sensitive adhesive layer of the second type is a pressure-sensitive adhesive layer that is not photocured and is a photocurable pressure-sensitive adhesive composition formed into a sheet shape. The pressure-sensitive adhesive layer of the second type contains a photopolymerizable compound in an unreacted state, so that the pressure-sensitive adhesive layer has photocurability.
[0133] The photocurable pressure-sensitive adhesive composition used to form the pressure-sensitive adhesive layer of the second type contains a polymer, a photopolymerizable compound, and a photopolymerization initiator.
[0134] (polymer) As the polymer contained in the pressure-sensitive adhesive composition, various polymers can be used as in the first embodiment, and an acrylic polymer is preferably used. The monomer components constituting the acrylic polymer are the same as in the first embodiment.
[0135] In order to introduce a crosslinked structure by a crosslinking agent described later, the monomer components constituting the polymer preferably contain a hydroxyl group-containing monomer and / or a carboxyl group-containing monomer. For example, when an isocyanate-based crosslinking agent is used, it is preferable to contain a hydroxyl group-containing monomer as a monomer component. When an epoxy-based crosslinking agent is used, it is preferable to contain a carboxyl group-containing monomer as a monomer.
[0136] In the second embodiment, since photocuring is not performed on the substrate, a polymer having a relatively large molecular weight is used as the polymer contained in the photocurable adhesive composition in order to form a solid (standard) adhesive layer. The weight average molecular weight of the polymer is, for example, about 100,000 to 2,000,000.
[0137] Since the high molecular weight polymer is a solid, the pressure-sensitive adhesive composition is preferably a solution in which the polymer is dissolved in an organic solvent. For example, the polymer solution can be obtained by solution polymerization of the monomer components. The polymer solution may be prepared by dissolving a solid polymer in an organic solvent.
[0138] As the solvent for solution polymerization, ethyl acetate, toluene, etc. are generally used. The solution concentration is usually about 20 to 80% by weight. As the polymerization initiator, thermal polymerization initiators such as azo initiators, peroxide initiators, and redox initiators (for example, a combination of persulfate and sodium bisulfite, a combination of peroxide and sodium ascorbate) are preferably used. The amount of the polymerization initiator used is not particularly limited, but for example, about 0.005 to 5 parts by weight, more preferably about 0.02 to 3 parts by weight, is preferred based on 100 parts by weight of the total amount of the monomer components forming the polymer.
[0139] (Photopolymerizable compound) In the second form, the photopolymerizable compound contained in the pressure-sensitive adhesive composition is the same as that described above for the first form, and a compound having one or more photopolymerizable functional groups is used.
[0140] (Photopolymerization initiator) In the second form, the photopolymerization initiator contained in the pressure-sensitive adhesive composition is the same as that described above for the first form, and those having an absorption maximum in the wavelength region of 330 to 400 nm are preferred. The amount of the photopolymerization initiator is about 0.01 to 10 parts by weight, preferably about 0.05 to 5 parts by weight, based on 100 parts by weight of the polymer.
[0141] (Colorant) The pressure-sensitive adhesive composition used in the second form may contain a colorant. In particular, it is preferable that the photocurable pressure-sensitive adhesive composition forming the first pressure-sensitive adhesive layer 1 further contains a colorant. When the photocurable pressure-sensitive adhesive composition forming the first pressure-sensitive adhesive layer 1 contains a colorant, the transmittance of the first pressure-sensitive adhesive layer 1 to visible light decreases, which is preferable for the configuration where T1 and T2 satisfy T1 < T2. The first pressure-sensitive adhesive layer 1 with reduced transmittance to visible light and imparted light-shielding property seals the space between the metal wiring layer 6 and the LED chip of the self-luminous display device (mini / micro LED display device) of the present embodiment, thereby preventing reflection by the metal wiring or the like, preventing color mixing between LED chips, and improving the contrast of the image.
[0142] The colorant contained in the pressure-sensitive adhesive composition used in the second embodiment is the same as that described above for the first embodiment, and preferably has an average transmittance at wavelengths of 330 to 400 nm greater than the average transmittance at wavelengths of 400 to 700 nm.
[0143] (Crosslinking agent) The second type of pressure-sensitive adhesive composition preferably contains a crosslinking agent capable of crosslinking with the polymer. Specific examples of the crosslinking agent for introducing a crosslinked structure into the polymer include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, carbodiimide-based crosslinking agents, and metal chelate-based crosslinking agents. Among them, isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred because they have high reactivity with the hydroxyl group or carboxyl group of the polymer and are easy to introduce a crosslinked structure. These crosslinking agents react with functional groups such as hydroxyl groups and carboxyl groups introduced into the polymer to form a crosslinked structure.
[0144] As the isocyanate crosslinking agent, a polyisocyanate having two or more isocyanate groups in one molecule is used. Examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as butylene diisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-tolylene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; trimethylolpropane / Examples of isocyanate adducts include tolylene diisocyanate trimer adducts (e.g., "Coronate L" manufactured by Tosoh), trimethylolpropane / hexamethylene diisocyanate trimer adducts (e.g., "Coronate HL" manufactured by Tosoh), trimethylolpropane adducts of xylylene diisocyanate (e.g., "Takenate D110N" manufactured by Mitsui Chemicals, and isocyanurate of hexamethylene diisocyanate (e.g., "Coronate HX" manufactured by Tosoh).
[0145] The epoxy crosslinking agent is a polyfunctional epoxy compound having two or more epoxy groups in one molecule. The epoxy group of the epoxy crosslinking agent may be a glycidyl group. Examples of epoxy crosslinking agents include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidylaniline, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, neopentyl glycol diglycidyl ether, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether, sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, o-phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, and bisphenol-S-diglycidyl ether. As the epoxy-based crosslinking agent, commercially available products such as "Denacol" manufactured by Nagase ChemteX, and "Tetrad X" and "Tetrad C" manufactured by Mitsubishi Gas Chemical may be used.
[0146] The amount of the crosslinking agent is about 0.01 to 5 parts by weight, and may be 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.2 parts by weight or more, and may be 3 parts by weight or less, 2 parts by weight or less, or 1 part by weight or less, relative to 100 parts by weight of the polymer.
[0147] (Other Ingredients) The pressure-sensitive adhesive composition of the second embodiment may contain, in addition to the above-mentioned components, an oligomer, a tackifier, a silane coupling agent, a chain transfer agent, a plasticizer, a softener, an antidegradant, a filler, an antioxidant, a surfactant, an antistatic agent, etc.
[0148] <Solvent-based pressure-sensitive adhesive composition> In this embodiment, the first pressure-sensitive adhesive layer 1 and the second pressure-sensitive adhesive layer 2 may be pressure-sensitive adhesive layers (third form) formed from a solvent-based pressure-sensitive adhesive composition. The solvent-based pressure-sensitive adhesive composition contains at least a polymer and a solvent, and may also contain a crosslinking agent. That is, the solvent-based pressure-sensitive adhesive composition used to form the pressure-sensitive adhesive layer of the third form contains a polymer and a solvent, and may also contain a crosslinking agent as necessary.
[0149] [Third form] The pressure-sensitive adhesive layer of the third embodiment can be formed by applying a solvent-based pressure-sensitive adhesive composition containing a polymer and a solvent, and optionally a crosslinking agent, onto a release film, and then drying and removing the solvent.
[0150] The solvent-based pressure-sensitive adhesive composition used to form the pressure-sensitive adhesive layer of the third embodiment contains a polymer and a solvent, and optionally contains a crosslinking agent.
[0151] (polymer) As the polymer contained in the solvent-based pressure-sensitive adhesive composition, various polymers can be used as in the first embodiment, and an acrylic polymer is preferably used. The monomer components constituting the acrylic polymer are the same as in the first embodiment.
[0152] In the third embodiment, in order to form a solid (standard) pressure-sensitive adhesive layer on a substrate, a polymer having a relatively large molecular weight is used as the polymer contained in the solvent-based pressure-sensitive adhesive composition. The weight-average molecular weight of the polymer is, for example, about 100,000 to 2,000,000.
[0153] The acrylic polymer contained in the solvent-based pressure-sensitive adhesive composition of the third embodiment may be a (meth)acrylic block copolymer. When the first pressure-sensitive adhesive layer 1 and / or the second pressure-sensitive adhesive layer 2 are formed from a solvent-based pressure-sensitive adhesive composition containing a (meth)acrylic block copolymer, the composition has excellent step absorbency and processability, so that the steps of the LED chips arranged on the substrate of the display panel can be sealed without leaving any air bubbles, and the processability is also excellent, so that the pressure-sensitive adhesive layer is unlikely to protrude from the edge during storage.
[0154] In this embodiment, the adhesive composition forming the first adhesive layer 1 is preferably a solvent-based adhesive composition containing a (meth)acrylic block copolymer. With this configuration, the first adhesive layer 1 has excellent step absorbency and excellent processability, and can seal multiple LED chips and metal wiring arranged on a display panel substrate without leaving any air bubbles at the steps, thereby preventing color mixing between the LED chips, improving the contrast of the image, and efficiently preventing reflection from metal wiring and the like.
[0155] In this embodiment, it is preferable that the (meth)acrylic block copolymer has a high Tg segment having a glass transition temperature of 0° C. or more and 100° C. or less, and a low Tg segment having a glass transition temperature of −100° C. or more and less than 0° C., and has tan δ peaks in the region of 0° C. or more and the region of less than 0° C., respectively.
[0156] In this specification, a "high Tg segment having a glass transition temperature of 0°C or more and 100°C or less" may be referred to simply as a "high Tg segment," a "low Tg segment having a glass transition temperature of -100°C or more and less than 0°C" may be referred to simply as a "low Tg segment," a tan δ peak in the region of 0°C or more may be referred to simply as a "high temperature region tan δ peak," a tan δ peak in the region of less than 0°C may be referred to simply as a "low temperature region tan δ peak," a (meth)acrylic block copolymer having the high Tg segment, the low Tg segment, the high temperature region tan δ peak and the low temperature region tan δ peak may be referred to simply as a "(meth)acrylic block copolymer A," and a solvent-based pressure-sensitive adhesive composition containing the (meth)acrylic block copolymer A may be referred to simply as a "solvent-based pressure-sensitive adhesive composition A."
[0157] The term "segment" in the high Tg segment and low Tg segment refers to a partial structure constituting each block unit of the (meth)acrylic block copolymer A.
[0158] The structure of the (meth)acrylic block copolymer A may be a linear block copolymer, a branched (star-shaped) block copolymer, or a mixture thereof. The structure of such a block copolymer may be appropriately selected depending on the desired physical properties of the block copolymer, but from the viewpoints of cost and ease of production, a linear block copolymer is preferable. In addition, the linear block copolymer may have any structure (arrangement), but from the viewpoints of the physical properties of the linear block copolymer or the physical properties of the solvent-based pressure-sensitive adhesive composition A, it is preferable that the linear block copolymer be (AB) n Type, (AB) n It is preferable that the block copolymer has at least one structure selected from the group consisting of -A type (n is an integer of 1 or more, for example, an integer of 1 to 3). In these structures, A and B mean segments composed of different monomer compositions. In this specification, the segment represented by A constituting the linear block copolymer may be referred to as the "A segment", and the segment represented by B may be referred to as the "B segment".
[0159] Among these, from the viewpoints of ease of production and physical properties of the solvent-type pressure-sensitive adhesive composition A, an AB-type diblock copolymer represented by AB and an ABA-type triblock copolymer represented by ABA are preferred, and an ABA-type triblock copolymer is more preferred. In an ABA-type triblock copolymer, the crosslinking structure between block copolymers becomes more advanced due to pseudo-crosslinking between the A segments at both ends, and it is considered that the cohesive force of the block copolymer is improved, and higher adhesion (adhesive force) can be expressed. In an ABA-type triblock copolymer, the two A segments located at both ends may be the same or different from each other.
[0160] When the (meth)acrylic block copolymer A is an ABA triblock copolymer, at least one of the two A segments and one B segment (total of three) may be a high Tg segment and at least the other one may be a low Tg segment. From the viewpoint of ease of production and physical properties of the solvent-type pressure-sensitive adhesive composition A, an ABA triblock copolymer in which the A segment is the high Tg segment and the B segment is the low Tg segment is preferred. In this case, an ABA triblock copolymer in which at least one of the two A segments is a high Tg segment and the B segment is a low Tg segment is preferred, and an ABA triblock copolymer in which both of the two A segments are high Tg segments and the B segment is a low Tg segment is more preferred.
[0161] The glass transition temperature (Tg) of the high Tg segment constituting the (meth)acrylic block copolymer A is, as described above, 0°C or more and 100°C or less. When the Tg of the high Tg segment is in this range, the storage modulus of the solvent-type pressure-sensitive adhesive composition A at room temperature (25°C) can be easily controlled to a high value, and the solvent-type pressure-sensitive adhesive composition A is hard and has excellent processability, and the storage modulus is significantly reduced in the range exceeding 50°C, resulting in a highly fluid pressure-sensitive adhesive composition. From the viewpoint of improving the processability of the solvent-type pressure-sensitive adhesive composition A at room temperature (25°C), the Tg of the high Tg segment is preferably 4°C or more, more preferably 6°C or more, even more preferably 8°C or more, even more preferably 10°C or more, and particularly preferably 12°C or more. On the other hand, from the viewpoint that the storage modulus (G') of the solvent-based pressure-sensitive adhesive composition A significantly decreases and the composition tends to become highly fluid in the range above 50°C, the Tg of the high Tg segment is preferably 90°C or less, more preferably 85°C or less, even more preferably 60°C or less, even more preferably 50°C or less, and particularly preferably 35°C or less.
[0162] The Tg of the low Tg segment constituting the (meth)acrylic block copolymer A is, as described above, -100°C or more and less than 0°C. When the glass Tg of the low Tg segment is in this range, only the low Tg segment becomes fluid at room temperature (25°C), and there is a tendency that the solvent-type pressure-sensitive adhesive composition A can be given a moderate adhesive strength while ensuring processability. From the viewpoint that the storage modulus of the solvent-type pressure-sensitive adhesive composition A is not likely to decrease at room temperature (25°C) and the processability can be improved, the Tg of the low Tg segment is preferably -95°C or more, more preferably -90°C or more, and even more preferably -80°C or more. On the other hand, from the viewpoint that the solvent-type pressure-sensitive adhesive composition A can be improved in moderate adhesive strength and processability at room temperature (25°C), the Tg of the low Tg segment is preferably -5°C or less, more preferably -10°C or less, even more preferably -20°C or less, even more preferably -30°C or less, and particularly preferably -40°C or less.
[0163] The difference in Tg between the high Tg segment and the low Tg segment constituting the (meth)acrylic block copolymer A (Tg of high Tg segment - Tg of low Tg segment) is not particularly limited, but from the viewpoints that the storage modulus of the solvent-based pressure-sensitive adhesive composition A at room temperature (25°C) can be easily controlled to a high level, the composition is hard and excellent in processability, and the storage modulus significantly decreases in the range above 50°C to form a highly fluid pressure-sensitive adhesive composition, the difference is preferably 30°C or higher, more preferably 35°C or higher, more preferably 40°C or higher, more preferably 45°C or higher, even more preferably 50°C or higher, particularly preferably 55°C or higher, and is preferably 120°C or lower, more preferably 115°C or lower, more preferably 110°C or lower, more preferably 105°C or lower, even more preferably 100°C or lower, particularly preferably 95°C or lower.
[0164] The glass transition temperatures (Tg) of the high Tg segment and low Tg segment constituting the (meth)acrylic block copolymer A are calculated glass transition temperatures calculated from the following Fox formula: This calculated glass transition temperature is calculated based on the type and amount of each monomer component constituting the high Tg segment or low Tg segment of the (meth)acrylic block copolymer A, and therefore can be adjusted by selecting the type and amount of the monomer component of each segment.
[0165] The calculated glass transition temperature (calculated Tg) can be calculated from the following Fox formula [1]. 1 / Calculation Tg=W1 / Tg(1)+W2 / Tg(2)+···+Wn / Tg(n) [1] Here, W1, W2, ...Wn mean the weight fractions (% by weight) of monomer component (1), monomer component (2), ...monomer component (n) that make up the copolymer, relative to the total monomer components, and Tg(1), Tg(2), ...Tg(n) mean the glass transition temperatures (units: absolute temperature: K) of the homopolymer of monomer component (1), monomer component (2), ...monomer component (n). The glass transition temperature of homopolymers is known from various documents and catalogs, and is described, for example, in J. Brandup, EH Immergut, EA Grulke: Polymer Handbook: JOHN WILEY & SONS, Inc. For monomers for which no numerical value is given in the various documents, a value measured by a general thermal analysis, for example, differential thermal analysis or dynamic viscoelasticity measurement method, can be used.
[0166] The temperature range in which the high-temperature region tan δ peak of the (meth)acrylic block copolymer A appears is 0° C. or higher (for example, 0° C. or higher and 100° C. or lower) as described above. The high-temperature region tan δ peak being in this temperature range makes it easier to control the storage modulus of the solvent-type pressure-sensitive adhesive composition A at room temperature (25° C.) to a high level, and the composition is hard and has excellent processability, and the storage modulus is significantly reduced in the range exceeding 50° C., resulting in a highly fluid pressure-sensitive adhesive composition. From the viewpoint of improving the processability of the solvent-type pressure-sensitive adhesive composition A at room temperature (25° C.), the temperature in which the high-temperature region tan δ peak appears is preferably 3° C. or higher, more preferably 6° C. or higher, even more preferably 9° C. or higher, even more preferably 12° C. or higher, and particularly preferably 15° C. or higher. On the other hand, from the viewpoint that the storage modulus (G') of the solvent-based pressure-sensitive adhesive composition A significantly decreases and the composition tends to become highly fluid in the range above 50°C, the temperature at which the high temperature range tan δ peak appears is preferably 90°C or lower, more preferably 80°C or lower, even more preferably 70°C or lower, even more preferably 65°C or lower, and particularly preferably 60°C or lower.
[0167] The temperature range in which the low-temperature region tan δ peak of the (meth)acrylic block copolymer A appears is less than 0°C (for example, -100°C or more and less than 0°C) as described above. When the low-temperature region tan δ peak is in this temperature range, only the low Tg segment is fluidized at room temperature (25°C), and there is a tendency that the solvent-type pressure-sensitive adhesive composition A can be given a moderate adhesive strength while ensuring processability. From the viewpoint that the storage modulus of the solvent-type pressure-sensitive adhesive composition A is unlikely to decrease at room temperature (25°C) and the processability can be improved, the temperature in which the low-temperature region tan δ peak appears is preferably -95°C or more, more preferably -90°C or more, even more preferably -80°C or more, and even more preferably -70°C or more. On the other hand, from the viewpoint of being able to improve the appropriate adhesive strength and processability of the solvent-based pressure-sensitive adhesive composition A at room temperature (25°C), the temperature at which the low temperature region tan δ peak appears is preferably -5°C or lower, more preferably -10°C or lower, even more preferably -20°C or lower, even more preferably -30°C or lower, and particularly preferably -40°C or lower.
[0168] The maximum value of the tan δ peak in the high temperature region is not particularly limited, but is preferably 0.5 to 3.0. The maximum value of the tan δ peak in the high temperature region in this range is preferable in that excellent processability and shape stability of the (meth)acrylic block copolymer A can be realized. The maximum value of the tan δ peak in the high temperature region is preferably 0.6 or more, more preferably 0.7 or more, in that excellent processability can be realized. In addition, the maximum value of the tan δ peak in the high temperature region is preferably 2.5 or less, more preferably 2.2 or less, in that dents are unlikely to occur.
[0169] The maximum value of the tan δ peak in the low temperature region is not particularly limited, but is preferably 0.1 to 2.0. The maximum value of the tan δ peak in the low temperature region in this range is preferable in that excellent processability and shape stability of the (meth)acrylic block copolymer A can be realized. The maximum value of the tan δ peak in the high temperature region is preferably 0.2 or more, more preferably 0.3 or more, in that excellent processability can be realized. In addition, the maximum value of the tan δ peak in the low temperature region is preferably 1.5 or less, more preferably 1 or less, in that dents are unlikely to occur.
[0170] The high-temperature region tan δ peak and the low-temperature region tan δ peak, as well as the temperatures at which they appear and their maximum values, are measured by dynamic viscoelasticity measurement.
[0171] The (meth)acrylic block copolymer A is composed of a plurality of segments (including a high Tg segment and a low Tg segment) obtained by polymerizing monomer components, and the monomer components include a monomer having a (meth)acryloyl group in the molecule (acrylic monomer). The (meth)acrylic block copolymer A or each segment thereof preferably contains 70% by weight or more of an acrylic monomer relative to the total amount of monomer components (100% by weight), more preferably 80% by weight or more, and particularly preferably 90% by weight or more.
[0172] The acrylic monomer constituting the (meth)acrylic block copolymer A or each segment thereof (including the high Tg segment and the low Tg segment) contains, as the main monomer unit having the largest weight ratio, a monomer component derived from an acrylic acid alkyl ester having a linear or branched alkyl group and / or a methacrylic acid alkyl ester having a linear or branched alkyl group.
[0173] Examples of the (meth)acrylic acid alkyl ester having a linear or branched alkyl group for forming the segment of the (meth)acrylic block copolymer A include the above-mentioned specific examples of the (meth)acrylic acid alkyl ester having a linear alkyl group. As the (meth)acrylic acid alkyl ester for the segment, one type of (meth)acrylic acid alkyl ester may be used, or two or more types of (meth)acrylic acid alkyl esters may be used. As the (meth)acrylic acid alkyl ester for the segment, preferably, at least one selected from the group consisting of methyl acrylate, n-butyl acrylate, and 2-ethylhexyl acrylate, t-butyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, and isononyl acrylate is used.
[0174] The segment of the (meth)acrylic block copolymer A may contain a monomer unit derived from an alicyclic monomer. As the alicyclic monomer for forming the monomer unit of the segment, specific examples of the (meth)acrylic acid alkyl ester having the above alicyclic alkyl group may be mentioned. The alicyclic alkyl group may have a substituent. Examples of the substituent include a halogen atom (e.g., a fluorine atom, a chlorine atom, a bromine atom, an iodine atom), a linear or branched alkyl group having 1 to 6 carbon atoms (e.g., a methyl group, an ethyl group, an n-propyl group, an isopropyl group, etc.). The number of the substituents is not particularly limited and can be appropriately selected from 1 to 6. When there are two or more substituents, the two or more substituents may be the same or different. As the alicyclic monomer for the segment, one type of alicyclic monomer may be used, or two or more types of alicyclic monomers may be used. As the alicyclic monomer for the segment, preferably, a (meth)acrylic acid cycloalkyl ester having a cycloalkyl group having 4 to 10 carbon atoms which may have a substituent (for example, a linear or branched alkyl group having 1 to 6 carbon atoms), more preferably, at least one selected from the group consisting of cyclohexyl acrylate and 3,3,5-trimethylcyclohexyl (meth)acrylate is used.
[0175] The segment of the (meth)acrylic block copolymer A may contain a monomer unit derived from a hydroxyl group-containing monomer. The hydroxyl group-containing monomer is a monomer that has at least one hydroxyl group in the monomer unit. When the segment in the (meth)acrylic block copolymer A contains a hydroxyl group-containing monomer unit, the solvent-based pressure-sensitive adhesive composition A is likely to have adhesiveness and appropriate cohesive strength.
[0176] Examples of the hydroxyl-containing monomer for forming the monomer unit of the segment include the above-mentioned specific examples of the hydroxyl-containing monomer. As the hydroxyl-containing monomer for the segment, one type of hydroxyl-containing monomer may be used, or two or more types of hydroxyl-containing monomers may be used. As the hydroxyl-containing monomer for the segment, a hydroxyl-containing (meth)acrylic acid ester is preferable, and at least one selected from the group consisting of 2-hydroxyethyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl acrylate, 2-hydroxypropyl methacrylate, 4-hydroxybutyl acrylate, and 4-hydroxybutyl methacrylate is more preferable.
[0177] The segment of the (meth)acrylic block copolymer A may contain a monomer unit derived from a nitrogen atom-containing monomer. The nitrogen atom-containing monomer is a monomer that has at least one nitrogen atom in the monomer unit. When the segment of the (meth)acrylic block copolymer A contains a nitrogen atom-containing monomer unit, hardness and good adhesive reliability are easily obtained in the solvent-based pressure-sensitive adhesive composition A.
[0178] As the nitrogen atom-containing monomer for forming the segment, the specific examples of the nitrogen atom-containing monomers mentioned above can be mentioned. As the nitrogen atom-containing monomer for the acrylic polymer, one kind of nitrogen atom-containing monomer may be used, or two or more kinds of nitrogen atom-containing monomers may be used. As the nitrogen atom-containing monomer for the segment, N-vinyl-2-pyrrolidone is preferably used.
[0179] The segment of the (meth)acrylic block copolymer A may contain a monomer unit derived from a carboxyl group-containing monomer. The carboxyl group-containing monomer is a monomer having at least one carboxyl group in the monomer unit. When the segment of the (meth)acrylic block copolymer A contains a carboxyl group-containing monomer unit, good adhesion reliability may be obtained in the solvent-based pressure-sensitive adhesive composition A.
[0180] The carboxyl group-containing monomer for forming the monomer unit of the segment may be the specific example of the carboxyl group-containing monomer described above. As the carboxyl group-containing monomer for the segment, one type of carboxyl group-containing monomer may be used, or two or more types of carboxyl group-containing monomers may be used. As the carboxyl group-containing monomer for the segment, acrylic acid is preferably used.
[0181] Further, examples of the monomer units for forming the segments include the above-mentioned other monomers. The content of the other monomers in the monomer units constituting the segments of the (meth)acrylic block copolymer A is not particularly limited as long as it is 30% by weight or less based on the total amount of the monomer components (100% by weight), and is appropriately selected within a range that does not impair the effects of the present invention.
[0182] As a monomer component constituting the high Tg segment of the (meth)acrylic block copolymer A, from the viewpoint of easily controlling the Tg of the high Tg segment within a predetermined range and imparting the desired physical properties to the (meth)acrylic block copolymer A, a (meth)acrylic acid alkyl ester having a linear alkyl group having 1 to 3 carbon atoms (hereinafter, "(meth)acrylic acid C") is used. 1-3 (meth)acrylic acid alkyl ester having a branched alkyl group with 3 or 4 carbon atoms (hereinafter referred to as "(meth)acrylic acid C 3-4 It is preferable that the copolymer contains at least one monomer selected from the group consisting of branched alkyl esters (sometimes referred to as "branched alkyl esters") and alicyclic monomers. Since homopolymers of these monomers have relatively high Tg, by containing a monomer selected from these monomers as a monomer component constituting the high Tg segment, it is easy to control the Tg of the high Tg segment within the specified range of the present invention.
[0183] The alicyclic monomer is preferably a (meth)acrylic acid cycloalkyl ester having a cycloalkyl group having 4 to 10 carbon atoms which may have a substituent (e.g., a linear or branched alkyl group having 1 to 6 carbon atoms), more preferably a cycloalkyl acrylate having a cycloalkyl group having 4 to 10 carbon atoms which may have a substituent (e.g., a linear or branched alkyl group having 1 to 6 carbon atoms), and particularly preferably cyclohexyl acrylate (Tg of homopolymer: 15°C) or 3,3,5-trimethylcyclohexyl (meth)acrylate (Tg of homopolymer: 52°C).
[0184] When an alicyclic monomer is contained as a monomer component constituting the high Tg segment, the content of the alicyclic monomer relative to the total amount of monomer components (100 wt%) is, from the viewpoint of easily controlling the Tg of the high Tg segment within a predetermined range and imparting desired physical properties to the (meth)acrylic block copolymer A, preferably 10 wt% or more (for example, 10 to 100 wt%), more preferably 20 wt% or more, more preferably 30 wt% or more, more preferably 30 wt% or more, more preferably 40 wt% or more, more preferably 50 wt% or more, more preferably 60 wt% or more, more preferably 70 wt% or more, more preferably 80 wt% or more, more preferably 80 wt% or more, even more preferably 90 wt% or more, and particularly preferably 95 wt% or more.
[0185] The (meth)acrylic acid C 1-3 As a linear alkyl ester, acrylic acid C 1-3 Linear alkyl esters are preferred, with methyl acrylate (Tg of homopolymer: 8° C.) being particularly preferred. The (meth)acrylic acid C 3-4 As branched alkyl esters, acrylic acid C 3-4 Branched alkyl esters are preferred, with t-butyl acrylate (Tg of homopolymer: 35° C.) being particularly preferred.
[0186] (Meth)acrylic acid C is used as a monomer component of the high Tg segment. 1-3Linear alkyl ester and / or (meth)acrylic acid C 3-4 When it contains a branched alkyl ester, (meth)acrylic acid C 1-3 Linear alkyl ester and / or (meth)acrylic acid C 3-4 The content of the branched alkyl ester relative to the total amount of monomer components (100% by weight), from the viewpoint of easily controlling the Tg of the high Tg segment within a predetermined range and imparting desired physical properties to the (meth)acrylic block copolymer A, is preferably 10% by weight or more (for example, 10 to 100% by weight), more preferably 20% by weight or more, more preferably 30% by weight or more, more preferably 30% by weight or more, more preferably 40% by weight or more, more preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, and particularly preferably 95% by weight or more.
[0187] As a monomer component constituting the low Tg segment of the (meth)acrylic block copolymer A, from the viewpoint of easily controlling the Tg of the low Tg segment within a predetermined range and imparting desired physical properties to the (meth)acrylic block copolymer A, a (meth)acrylic acid alkyl ester having a linear or branched alkyl group having 4 to 18 carbon atoms (hereinafter referred to as "(meth)acrylic acid C") is used. 4-18 It is preferable that the (meth)acrylic acid C contains at least one selected from the group consisting of (meth)acrylic acid C alkyl esters) and hydroxyl group-containing monomers. 4-18 Since the homopolymer of the alkyl ester has a relatively low Tg, by containing it as a monomer component constituting the low Tg segment, it is easy to control the Tg of the low Tg segment within the range specified in the present invention. On the other hand, the hydroxyl group-containing monomer also has a relatively low Tg, and furthermore, it becomes easier to obtain adhesiveness and appropriate cohesive force in the (meth)acrylic block copolymer A. Therefore, it is preferable to use (meth)acrylic acid C as a monomer component constituting the low Tg segment of the (meth)acrylic block copolymer A. 4-18 It is more preferred to contain both an alkyl ester and a hydroxyl group-containing monomer.
[0188] The (meth)acrylic acid C 4-18 As alkyl esters, acrylic acid C 4-18 Alkyl esters are preferred, with butyl acrylate (homopolymer Tg: -55°C), 2-ethylhexyl acrylate (homopolymer Tg: -70°C), n-hexyl acrylate (homopolymer Tg: -57°C), n-octyl acrylate (homopolymer Tg: -65°C), and isononyl acrylate (homopolymer Tg: -58°C) being particularly preferred.
[0189] (Meth)acrylic acid C is used as a monomer component that constitutes the low Tg segment. 4-18 If it contains an alkyl ester, (meth)acrylic acid C 4-18 The content of the alkyl ester relative to the total amount of monomer components (100% by weight), from the viewpoint of easily controlling the Tg of the low Tg segment within a predetermined range and imparting desired physical properties to the (meth)acrylic block copolymer A, is preferably 10% by weight or more (for example, 10 to 100% by weight), more preferably 20% by weight or more, more preferably 30% by weight or more, more preferably 30% by weight or more, more preferably 40% by weight or more, more preferably 50% by weight or more, more preferably 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, more preferably 80% by weight or more, even more preferably 90% by weight or more, and particularly preferably 95% by weight or more.
[0190] The hydroxyl group-containing monomer is preferably a hydroxyl group-containing alkyl (meth)acrylate, and particularly preferably 4-hydroxybutyl acrylate (Tg of homopolymer: -65°C) or 2-hydroxyethyl acrylate (Tg of homopolymer: -15°C).
[0191] When a hydroxyl group-containing monomer is contained as a monomer component constituting the low Tg segment, the content of the hydroxyl group-containing monomer relative to the total amount of monomer components (100% by weight) is preferably 1% by weight or more, more preferably 1.5% by weight or more, more preferably 2% by weight or more, even more preferably 2.5% by weight or more, and particularly preferably 3% by weight or more, from the viewpoint of easily controlling the Tg of the low Tg segment within a predetermined range and imparting desired physical properties to the (meth)acrylic block copolymer A. On the other hand, the content of the hydroxyl group-containing monomer relative to the total amount of monomer components (100% by weight) is preferably 50% by weight or less, more preferably 40% by weight or less, more preferably 30% by weight or less, more preferably 20% by weight or less, even more preferably 10% by weight or less, and particularly preferably 5% by weight or less.
[0192] As a monomer component constituting the low Tg segment of the (meth)acrylic block copolymer A, (meth)acrylic acid C 4-18 In the case where both an alkyl ester and a hydroxyl group-containing monomer are contained, the hydroxyl group-containing monomer and (meth)acrylic acid C 4-18 Ratio of alkyl ester (hydroxyl group-containing monomer / (meth)acrylic acid C 4-18 The alkyl ester) is not particularly limited, but the lower limit is preferably 1 / 99, more preferably 1.5 / 98.5, more preferably 2 / 98, even more preferably 2.5 / 97.5, and particularly preferably 3 / 97, while the upper limit is 50 / 50, more preferably 40 / 60, more preferably 30 / 70, and even more preferably 20 / 80.
[0193] The (meth)acrylic block copolymer A can be produced by a living radical polymerization method of the above-mentioned monomer components. The living radical polymerization method is preferable in that, while maintaining the simplicity and versatility of conventional radical polymerization methods, termination reactions and chain transfer are unlikely to occur, and the growing end grows without being deactivated, making it easy to precisely control the molecular weight distribution and produce a polymer with a uniform composition.
[0194] In the living radical polymerization method, the high Tg segment may be produced first, and then a monomer for the low Tg segment may be polymerized onto the high Tg segment; or the low Tg segment may be produced first, and then a monomer for the high Tg segment may be polymerized onto the low Tg segment.
[0195] When the (meth)acrylic block copolymer A is an ABA type triblock copolymer, from the viewpoint of ease of production, it is preferred to produce the A segment first and then polymerize the B segment monomer onto the A segment.
[0196] The living radical polymerization method can be any known method without any particular limitation, and depending on the difference in the method for stabilizing the polymer growth terminal, there are methods such as a method using a transition metal catalyst (ATRP method), a method using a sulfur-based reversible addition-fragmentation chain transfer agent (RAFT agent) (RAFT method), and a method using an organic tellurium compound (TERP method). Among these methods, it is preferable to use the RAFT method from the viewpoints of the variety of monomers that can be used, the ease of molecular weight control, and the fact that metals do not remain in the solvent-based pressure-sensitive adhesive composition.
[0197] The RAFT method can be any known method without any particular limitation, and includes, for example, step 1 (first RAFT polymerization) of preparing a first segment by polymerizing a monomer component using a RAFT agent, and step 2 (second RAFT polymerization) of adding a second segment to the first segment by further adding and polymerizing a monomer component having a monomer composition different from that in step 1 to the first segment obtained in step 1. After the second RAFT polymerization, third, fourth... RAFT polymerizations may be further performed in the same manner as the second RAFT polymerization to further add third, fourth... segments.
[0198] The steps 1 and 2 can be carried out by known and commonly used methods, such as solution polymerization, emulsion polymerization, bulk polymerization, and polymerization by heat or active energy ray irradiation (thermal polymerization, active energy ray polymerization). Among them, the solution polymerization is preferred in terms of transparency, water resistance, cost, etc. It is preferable to carry out the polymerization while avoiding contact with oxygen in order to suppress polymerization inhibition by oxygen. For example, it is preferable to carry out the polymerization under a nitrogen atmosphere.
[0199] When the (meth)acrylic block copolymer A is an ABA type triblock copolymer, it is preferable to prepare the copolymer by preparing an A segment in the above step 1 and adding a B segment to the obtained A segment in the above step 2. In this case, it is preferable that the A segment is a high Tg segment and the B segment is a low Tg segment.
[0200] As the RAFT agent, any known agent can be used without any particular limitation. For example, a compound represented by the following formula (1), formula (2), or formula (3) (trithiocarbonate, dithioester, dithiocarbonate) is preferable. [ka] [ka] [ka]
[0201] In formula (1), formula (2), or formula (3) [formulas (1) to (3)], R 1a and R 1b R may be the same or different and represents a hydrogen atom, a hydrocarbon group, or a cyano group. 1c represents a hydrocarbon group which may have a cyano group. 1a , R 1b , and R 1cExamples of the hydrocarbon group as R include hydrocarbon groups having 1 to 20 carbon atoms (straight-chain, branched-chain, or cyclic saturated or unsaturated hydrocarbon groups, etc.), and among these, hydrocarbon groups having 1 to 12 carbon atoms are preferred. Specific examples of the hydrocarbon group include straight-chain, branched-chain, or cyclic alkyl groups having 1 to 12 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, cyclohexyl, dodecyl, and octadecyl; aryl groups having 6 to 12 carbon atoms, such as phenyl; and arylalkyl groups having a total of 7 to 10 carbon atoms, such as benzyl and phenethyl. 1c Examples of the hydrocarbon group having a cyano group as the substituent include the above-mentioned hydrocarbon groups in which 1 to 3 hydrogen atoms have been substituted with cyano groups.
[0202] In formulas (1) to (3), R 2 represents a hydrocarbon group or a group in which some of the hydrogen atoms of the hydrocarbon group have been substituted with a carboxyl group (e.g., a carboxyalkyl group). Examples of the hydrocarbon group include hydrocarbon groups having 1 to 20 carbon atoms (such as linear, branched, or cyclic saturated or unsaturated hydrocarbon groups), and among these, hydrocarbon groups having 1 to 12 carbon atoms are preferred. Specific examples of the hydrocarbon group include linear, branched, or cyclic alkyl groups having 1 to 12 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, a cyclohexyl group, a dodecyl group, or an octadecyl group; and arylalkyl groups having a total of 7 to 10 carbon atoms, such as a benzyl group or a phenethyl group.
[0203] In the RAFT method, polymerization proceeds by reacting a raw material monomer so as to be inserted between a sulfur atom in a RAFT agent represented by any of the formulas (1) to (3) and a methylene group adjacent to the sulfur atom.
[0204] Many of the RAFT agents are commercially available. Those that are not commercially available can be easily synthesized by known or conventional methods. In the present invention, the RAFT agents can be used alone or in combination of two or more.
[0205] Examples of the RAFT agent include trithiocarbonates such as dibenzyl trithiocarbonate and S-cyanomethyl-S-dodecyl trithiocarbonate; dithioesters such as cyanoethyl dithiopropionate, benzyl dithiopropionate, benzyl dithiobenzoate and acetoxyethyl dithiobenzoate; and dithiocarbonates such as O-ethyl-S-(1-phenylethyl)dithiocarbonate, O-ethyl-S-(2-propoxyethyl)dithiocarbonate and O-ethyl-S-(1-cyano-1-methylethyl)dithiocarbonate. Of these, trithiocarbonates are preferred, and trithiocarbonates having a symmetrical structure in formula (1) are more preferred, with dibenzyl trithiocarbonate and bis{4-[ethyl-(2-acetyloxyethyl)carbamoyl]benzyl}trithiocarbonate being particularly preferred.
[0206] The step 1 can be carried out by polymerizing the monomer components in the presence of a RAFT agent. The amount of the RAFT agent used in step 1 is usually 0.05 to 20 parts by weight, and preferably 0.05 to 10 parts by weight, based on 100 parts by weight of the total amount of the monomer components. With such an amount, the reaction can be easily controlled, and the weight average molecular weight of the resulting segment can be easily controlled. The step 2 can be carried out by adding a monomer component to the polymerization reaction mixture obtained in the step 1 and further polymerizing the mixture.
[0207] The RAFT method is preferably carried out in the presence of a polymerization initiator. For example, the polymerization initiator may be a normal organic polymerization initiator, specifically, peroxides and azo compounds, among which azo compounds are preferred. The polymerization initiator may be used alone or in combination of two or more.
[0208] Examples of peroxide-based polymerization initiators include benzoyl peroxide and tert-butyl permaleate. Examples of the azo compound include 2,2'-azobisisobutyronitrile, 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2'-azobis(2-cyclopropylpropionitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2-(carbamoylazo)isobutyronitrile, 2-phenylazo-4-methoxy-2,4- Dimethylvaleronitrile, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis(isobutylamide) dihydrate, 4,4'-azobis(4-cyanopentanoic acid), 2,2'-azobis(2-cyanopropanol), dimethyl-2,2'-azobis(2-methylpropionate), 2,2'-azobis[2-methyl-N-(2-hydroxyethyl)propionamide].
[0209] The amount of the polymerization initiator used is usually 0.001 to 2 parts by weight, and preferably 0.002 to 1 part by weight, based on 100 parts by weight of the total amount of the monomer components. With such an amount, it is easy to control the weight average molecular weight of the obtained segment.
[0210] The RAFT method may be a bulk polymerization that does not use a polymerization solvent, but it is preferable to use a polymerization solvent. Examples of the polymerization solvent include aromatic hydrocarbons such as benzene, toluene, and xylene; aliphatic hydrocarbons such as n-pentane, n-hexane, n-heptane, and n-octane; alicyclic hydrocarbons such as cyclopentane, cyclohexane, cycloheptane, and cyclooctane; halogenated hydrocarbons such as chloroform, carbon tetrachloride, 1,2-dichloroethane, and chlorobenzene; ethers such as diethyl ether, diisopropyl ether, 1,2-dimethoxyethane, dibutyl ether, tetrahydrofuran, dioxane, anisole, phenylethyl ether, and diphenyl ether; esters such as ethyl acetate, propyl acetate, butyl acetate, and methyl propionate; ketones such as acetone, methyl ethyl ketone, diethyl ketone, methyl isobutyl ketone, and cyclohexanone; amides such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone; nitriles such as acetonitrile and benzonitrile; and sulfoxides such as dimethyl sulfoxide and sulfolane. The polymerization solvent may be used alone or in combination of two or more.
[0211] The amount of the polymerization solvent used is not particularly limited, and is, for example, preferably 0.01 mL or more, more preferably 0.05 mL or more, and even more preferably 0.1 mL or more, per 1 g of the monomer component, and is preferably 50 mL or less, more preferably 10 mL or less, and even more preferably 1 mL or less.
[0212] The reaction temperature in the RAFT method is usually 60 to 120°C, preferably 70 to 110°C, and is usually carried out under an inert gas atmosphere such as nitrogen gas. This reaction can be carried out under any condition of normal pressure, increased pressure, or reduced pressure, and is usually carried out at normal pressure. The reaction time is usually 1 to 20 hours, preferably 2 to 14 hours.
[0213] The polymerization reaction conditions for the RAFT method described above can be applied to steps 1 and 2, respectively.
[0214] After the polymerization reaction is completed, the target (meth)acrylic block copolymer A can be separated from the resulting reaction mixture by removing the solvent used and residual monomers by ordinary separation and purification means.
[0215] When the high Tg segment or low Tg segment of the (meth)acrylic block copolymer A is prepared in the above step 1, the weight average molecular weight (Mw) of the high Tg segment or low Tg segment is not particularly limited, but is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and further preferably 100,000 to 300,000. The Mw of the high Tg segment or low Tg segment within this range is suitable for achieving the above-mentioned effects of the present invention. When the (meth)acrylic block copolymer A has two or more high Tg segments or two or more low Tg segments, the above Mw is the sum of the Mw of the high Tg segments or the low Tg segments.
[0216] The weight average molecular weight (Mw) of the (meth)acrylic block copolymer A is not particularly limited, but is preferably 200,000 or more, more preferably 300,000 to 5,000,000, and even more preferably 400,000 to 2,500,000. The Mw of the (meth)acrylic block copolymer A within this range is suitable for achieving the above-mentioned effects of the present invention.
[0217] The molecular weight distribution (Mw / Mn) of the (meth)acrylic block copolymer A is not particularly limited, but is preferably greater than 1, more preferably 1.5 or more, even more preferably 2 or more, particularly preferably 2.5 or more, and is preferably 5 or less, more preferably 4.5 or less, even more preferably 4 or less, and particularly preferably 3.5 or less.
[0218] The weight average molecular weight (Mw) and the molecular weight distribution (Mw / Mn) are measured by a GPC method.
[0219] The content of the high Tg segment in the (meth)acrylic block copolymer A is preferably 10% by weight or more, more preferably 20% by weight or more, even more preferably 25% by weight or more, and particularly preferably 30% by weight or more, and is preferably 95% by weight or less, more preferably 90% by weight or less, and even more preferably 85% by weight or less, based on 100% by weight of the entire (meth)acrylic block copolymer A.
[0220] The content of the low Tg segment in the (meth)acrylic block copolymer A is preferably 5 wt % or more, more preferably 10 wt % or more, and even more preferably 15 wt % or more, based on 100 wt % of the entire (meth)acrylic block copolymer A; and is preferably 60 wt % or less, more preferably 50 wt % or less, even more preferably 40 wt % or less, and particularly preferably 30 wt % or less.
[0221] The content and ratio of each segment can be calculated from the weight average molecular weight (Mw) of each segment or the (meth)acrylic block copolymer A obtained in each step of the RAFT method, and can be controlled by the monomer charging ratio when forming each segment and the polymerization rate of each monomer, etc.
[0222] The content of the (meth)acrylic block copolymer A in the solvent-based pressure-sensitive adhesive composition A is not particularly limited, but from the viewpoint of obtaining excellent processability at room temperature (25°C) and excellent step absorbency in the range exceeding 50°C, the content is preferably 50 wt % or more (e.g., 50 to 100 wt %) relative to the total amount of the solvent-based pressure-sensitive adhesive composition A (total weight, 100 wt %), more preferably 60 wt % or more, even more preferably 80 wt % or more, and particularly preferably 90 wt % or more.
[0223] (solvent) Since the polymer in the third form is solid, the solvent-based pressure-sensitive adhesive composition is a solution in which the polymer is dissolved in an organic solvent. For example, the polymer solution can be obtained by solution polymerization of the monomer components. The polymer solution can also be prepared by dissolving the solid polymer in an organic solvent.
[0224] Generally, ethyl acetate, toluene, etc. are used as the solvent. The solution concentration is usually about 20 to 80% by weight.
[0225] As the polymerization initiator in the case of solution polymerization of the monomer component, thermal polymerization initiators such as azo initiators, peroxide initiators, and redox initiators (for example, a combination of persulfate and sodium bisulfite, a combination of peroxide and sodium ascorbate) are preferably used. The amount of the polymerization initiator used is not particularly limited, but for example, with respect to 100 parts by weight of the total amount of the monomer components forming the polymer, about 0.005 to 5 parts by weight is preferable, and about 0.02 to 3 parts by weight is more preferable.
[0226] (Colorant) The solvent-based pressure-sensitive adhesive composition used for forming the third-form pressure-sensitive adhesive layer may contain a colorant. In particular, it is preferable that the solvent-based pressure-sensitive adhesive composition forming the first pressure-sensitive adhesive layer 1 further contains a colorant. When the solvent-based pressure-sensitive adhesive composition forming the first pressure-sensitive adhesive layer 1 contains a colorant, the transmittance of the first pressure-sensitive adhesive layer 1 to visible light decreases, which is preferable for the configuration where the above T1 and the above T2 satisfy T1 < T2. The first pressure-sensitive adhesive layer 1 with reduced transmittance to visible light and imparted light-shielding property seals the space between the metal wiring layer 6 and the LED chip of the self-luminous display device (mini / micro LED display device) of the present embodiment, thereby preventing reflection by the metal wiring and the like, preventing color mixing between LED chips, and improving the contrast of the image.
[0227] The colorant may be a dye or a pigment as long as it can be dissolved or dispersed in the solvent-based pressure-sensitive adhesive composition. Dyes are preferred because low haze can be achieved even with a small amount of addition, and they do not have sedimentation properties like pigments and are easily uniformly distributed. Also, pigments are preferred because high color expressibility can be achieved even with a small amount of addition. When using a pigment as the colorant, it is preferably one with low or no conductivity. Also, when using a dye, it is preferably used in combination with an antioxidant or the like.
[0228] In the third embodiment, the colorant contained in the solvent-based pressure-sensitive adhesive composition includes an ultraviolet absorbing colorant in addition to the ultraviolet transmitting colorant described above in relation to the first embodiment.
[0229] Examples of ultraviolet-transmitting black pigments include "9050BLACK" and "UVBK-0001" manufactured by Tokushiki. Examples of ultraviolet-absorbing black dyes include "VALIFAST BLACK 3810" and "NUBIAN Black PA-2802" manufactured by Orient Chemical Industries. Examples of ultraviolet-absorbing black pigments include carbon black and titanium black.
[0230] The content of the colorant in the solvent-based pressure-sensitive adhesive composition is, for example, about 0.01 to 20 parts by weight relative to 100 parts by weight of the total amount of monomers, and may be appropriately set depending on the type of colorant, the color tone and light transmittance of the pressure-sensitive adhesive layer, etc. The colorant may be added to the composition as a solution or dispersion in which it is dissolved or dispersed in a suitable solvent.
[0231] (Crosslinking agent) The solvent-based pressure-sensitive adhesive composition of the third embodiment may contain a crosslinking agent capable of crosslinking with the above-mentioned polymer. When the solvent-based pressure-sensitive adhesive composition contains a (meth)acrylic block copolymer, the pressure-sensitive adhesive layer of the third embodiment has sufficient shape stability and therefore does not need to contain a crosslinking agent.
[0232] In the third embodiment, when the solvent-based pressure-sensitive adhesive composition contains a crosslinking agent, the crosslinking agent is the same as that described above for the second embodiment, and isocyanate-based crosslinking agents and epoxy-based crosslinking agents are preferred.
[0233] In the third embodiment, when the solvent-based pressure-sensitive adhesive composition contains a crosslinking agent, the content thereof is about 0.01 to 5 parts by weight, and may be 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.2 parts by weight or more, or may be 3 parts by weight or less, 2 parts by weight or less, or 1 part by weight or less, relative to 100 parts by weight of the polymer.
[0234] (Other Ingredients) The solvent-based pressure-sensitive adhesive composition of the third embodiment may contain, in addition to the above-mentioned components, an oligomer, a tackifier, a silane coupling agent, a chain transfer agent, a plasticizer, a softener, an antidegradant, a filler, an antioxidant, a surfactant, an antistatic agent, etc.
[0235] <Optical laminate> In this embodiment, the optical laminates 10 to 12 can be prepared by laminating the second pressure-sensitive adhesive layer 2 on the surface 3b of the substrate 3, and further laminating the first pressure-sensitive adhesive layer 1 thereon.
[0236] [First form] The method for laminating the second adhesive layer 2 of the first form on the surface 3b of the substrate 3 is not particularly limited, and can be performed, for example, by applying the photocurable adhesive composition onto a release film, forming it into a sheet, photocuring it to produce a sheet-like second adhesive layer 2, and then laminating it onto the surface 3b of the substrate 3.
[0237] The method for laminating the first adhesive layer 1 onto the second adhesive layer 2 laminated on the substrate 3 is not particularly limited, and can be, for example, by applying the photocurable adhesive composition onto a release film, forming it into a sheet, photocuring it to produce a sheet-like first adhesive layer 1, and then bonding it to the second adhesive layer laminated on the surface 3b of the substrate 3.
[0238] The photocurable adhesive composition is applied in a sheet (layer) on a release film, and the coating of the adhesive composition on the release film is irradiated with ultraviolet light to perform photocuring, thereby obtaining the first adhesive layer or the second adhesive layer of the first form. When performing photocuring, it is preferable to further attach a release film to the surface of the coating film, and irradiate ultraviolet light while the photocurable adhesive composition is sandwiched between two release films, thereby preventing polymerization inhibition due to oxygen. Before photocuring, the sheet-shaped coating film may be heated for the purpose of removing the solvent or dispersion medium of the colorant, etc. When removing the solvent, etc. by heating, it is preferable to perform the removal before attaching the release film.
[0239] As the film substrate of the release film, films made of various resin materials are used. Examples of the resin materials include polyester resins such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyarylate resins, and polyphenylene sulfide resins. Among these, polyester resins such as polyethylene terephthalate are particularly preferred. The thickness of the film substrate is preferably 10 to 200 μm, and more preferably 25 to 150 μm. Examples of materials for the release layer include silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, and fatty acid amide-based release agents. The thickness of the release layer is generally about 10 to 2000 nm.
[0240] As a method for applying the pressure-sensitive adhesive composition onto a release film, various methods such as roll coating, kiss roll coating, gravure coating, reverse coating, roll brush, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating can be used.
[0241] The thickness of the first adhesive layer 1 is not particularly limited, and may be appropriately set so that the upper part (image display side) of the light emitting element arranged on the display panel described later is covered with the second adhesive layer 2 while sufficiently sealing the light emitting element. For example, the thickness of the first adhesive layer is adjusted to be 0.1 to 2.0 times, preferably 0.2 to 1.5 times, more preferably 0.3 to 1.2 times the height of the light emitting element. Specifically, the thickness of the first adhesive layer is, for example, about 10 to 300 μm, and preferably 15 to 200 μm. Specifically, the thickness of the first adhesive layer may be 10 μm or more, 15 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more. In addition, when the first adhesive layer contains an ultraviolet-transmitting colorant, even if the thickness of the first adhesive layer is large, the photocurable adhesive composition can be photocured uniformly in the thickness direction. The thickness of the first adhesive layer may be 300 μm or less, 250 μm or less, or 200 μm or less.
[0242] The thickness of the second adhesive layer 2 is not particularly limited, and may be appropriately set so as to adequately seal the light emitting elements arranged on the display panel described below while allowing sufficient light transmission above the light emitting elements (image display side). Specifically, the thickness of the second adhesive layer is, for example, about 1 to 500 μm, more preferably 10 to 300 μm, and even more preferably 15 to 200 μm. Specifically, the thickness of the second adhesive layer may be 1 μm or more, 10 μm or more, 15 μm or more, 20 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more. The thickness of the second adhesive layer may be 400 μm or less, 300 μm or less, 250 μm or less, or 200 μm or less.
[0243] The total thickness of the first adhesive layer 1 and the second adhesive layer 2 is not particularly limited, and may be appropriately set to be equal to or greater than the height of the light emitting element arranged on the display panel described below so that the light emitting element can be sufficiently sealed. For example, the thickness of the adhesive layer is adjusted to be 1.0 to 4.0 times, preferably 1.1 to 3.0 times, more preferably 1.2 to 2.5 times, and even more preferably 1.3 to 2.0 times the height of the light emitting element. Specifically, the total thickness of the first adhesive layer 1 and the second adhesive layer 2 is, for example, about 11 to 800 μm, and may be 20 μm or more, 30 μm or more, 40 μm or more, or 50 μm or more. In addition, the total thickness of the first adhesive layer 1 and the second adhesive layer 2 may be, for example, 700 μm or less, 600 μm or less, 500 μm or less, or 400 μm or less.
[0244] The ratio of the thickness of the second adhesive layer to the thickness of the first adhesive layer (thickness of the second adhesive layer / thickness of the first adhesive layer) is not particularly limited, and may be appropriately set so that the upper part (image display side) of the light-emitting element arranged on a display panel described later is covered with the second adhesive layer while sufficiently sealing the light-emitting element. Specifically, (thickness of the second adhesive layer / thickness of the first adhesive layer) may be, for example, about 1.0 to 5.0, preferably 1.2 to 4.0, and more preferably 1.3 to 3.0.
[0245] By irradiating the photocurable adhesive composition coated in a layer on a release film with ultraviolet light, active species are generated from the photopolymerization initiator, the photopolymerizable compound is polymerized, and the liquid photocurable adhesive composition becomes a solid (standard) adhesive layer with an increase in the polymerization rate (a decrease in unreacted monomers). The light source for ultraviolet light irradiation is not particularly limited as long as it can irradiate light in a wavelength range to which the photopolymerization initiator contained in the photocurable adhesive composition is sensitive, and may be an LED light source, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, a xenon lamp, or the like.
[0246] The integrated light amount of the irradiation light is, for example, 100 to 5000 mJ / cm 2The polymerization rate (non-volatile content) of the pressure-sensitive adhesive layer made of the photocured product of the photocurable pressure-sensitive adhesive composition is preferably 80% or more, more preferably 85% or more, and even more preferably 90% or more. The polymerization rate may be 93% or more or 95% or more. In order to reduce the non-volatile content, the pressure-sensitive adhesive layer may be heated to remove volatile content such as residual monomers, unreacted polymerization initiator, and solvent.
[0247] When a release film is provided on both sides of the adhesive layer, the thickness of one release film and the thickness of the other release film may be the same or different. The release force when peeling off the release film temporarily attached to one side from the adhesive layer and the release force when peeling off the release film temporarily attached to the other side from the adhesive layer may be the same or different. When the release forces of both are different, the release film with a relatively small release force (light release film) is first peeled off from the second adhesive layer 2 and attached to the surface 3b of the base material 3, and then the release film with a relatively large release force (heavy release film) is peeled off from the second adhesive layer 2 to expose the second adhesive layer. Then, the light release film is peeled off from the first adhesive layer 1 and attached to the exposed second adhesive layer, thereby producing an optical laminate having the first adhesive layer and the second adhesive layer of the first form.
[0248] In addition, an optical laminate having the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer of the first form can also be produced in the same manner as above, except that the second adhesive layer is laminated on the substrate 3 by applying the photocurable pressure-sensitive adhesive composition to the surface 3b of the substrate 3, forming it into a sheet, attaching a release film to the surface of the coating, and irradiating with ultraviolet light.
[0249] When the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer contain a colorant, the layer has optical absorption in visible light. The visible light transmittance of the optical laminate of the first embodiment is, for example, 80% or less, and may be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less.
[0250] In the first embodiment, the visible light transmittance T1 of the first adhesive layer is not particularly limited, and may be, for example, 80% or less, 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less. When the visible light transmittance T1 of the first adhesive layer is 80% or less, the transmittance is easily made lower than the visible light transmittance T2 of the second adhesive layer, and as described above, by sealing between the metal wiring and the light-emitting elements of the self-luminous display device, it is possible to prevent reflection of the metal wiring and the like, prevent color mixing between the light-emitting elements, and improve contrast. In addition, as described above, when a colorant that absorbs less ultraviolet light than visible light is used in the first adhesive layer, the first adhesive layer has an average transmittance T UV is the average transmittance T for wavelengths from 400 to 700 nm VIS The average transmittance T of the first adhesive layer at wavelengths of 400 to 700 nm is greater than VIS The average transmittance T of the first pressure-sensitive adhesive layer at wavelengths of 330 to 400 nm is, for example, 80% or less, and may be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, or 10% or less. UV is preferably 5% or more, and may be 10% or more, 15% or more, 20% or more, or 25% or more. UV and T VIS Difference with T UV -T VIS may be 3% or more, 5% or more, 8% or more, or 10% or more.
[0251] In the first embodiment, the visible light transmittance T2 of the second adhesive layer is not particularly limited, and may be, for example, 85 to 100%, and may be 88% or more, 90% or more, or 92% or more. As described above, the light emitting efficiency is improved by covering the upper part (image display side) of the light emitting element of the self-luminous display device with the highly transparent second adhesive layer.
[0252] In the first embodiment, the shear storage modulus G'25°C of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer at a temperature of 25°C is, for example, about 10 to 1000 kPa, and may be 30 kPa or more, 50 kPa or more, 70 kPa or more, or 100 kPa or more, and may be 700 kPa or less, 500 kPa or less, 300 kPa or less, or 200 kPa or less. The shear storage modulus G'85°C of the pressure-sensitive adhesive layer at a temperature of 85°C is, for example, about 3 to 300 kPa, and may be 5 kPa or more, 7 kPa or more, or 10 kPa or more, and may be 200 kPa or less, 150 kPa or less, or 100 kPa or less. If the shear storage modulus of the pressure-sensitive adhesive layer is within the above range, it is possible to achieve both appropriate flexibility and adhesiveness. The shear storage modulus is a value measured by dynamic viscoelasticity measurement at a frequency of 1 Hz.
[0253] [Second form] An optical laminate having a pressure-sensitive adhesive layer of the second form can be prepared by coating the photocurable pressure-sensitive adhesive composition of the second form onto a release film, drying and removing the solvent as necessary to form a second pressure-sensitive adhesive layer, and attaching it to surface 3b of substrate 3. Next, the photocurable pressure-sensitive adhesive composition of the second form is coated onto a release film, drying and removing the solvent as necessary to form a first pressure-sensitive adhesive layer, and then attaching it to the second pressure-sensitive adhesive layer laminated on surface 3b of substrate 3.
[0254] Alternatively, an optical laminate having a pressure-sensitive adhesive layer of the second form can be prepared by coating the photocurable pressure-sensitive adhesive composition of the second form on the surface 3b of the substrate 3, and drying and removing the solvent as necessary to form a second pressure-sensitive adhesive layer. Next, the photocurable pressure-sensitive adhesive composition of the second form is coated on a release film, and the solvent is dried and removed as necessary to form a first pressure-sensitive adhesive layer, and then bonding the first pressure-sensitive adhesive layer to the second pressure-sensitive adhesive layer laminated on the surface 3b of the substrate 3.
[0255] When the photocurable adhesive composition contains a solvent, it is preferable to dry the solvent after coating the adhesive composition. As the drying method, a suitable method can be adopted depending on the purpose. The heating and drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and particularly preferably 70°C to 170°C. As the drying time, a suitable time can be adopted. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and particularly preferably 10 seconds to 10 minutes.
[0256] After coating the photocurable pressure-sensitive adhesive composition, heating is performed as necessary to introduce a crosslinked structure into the polymer. The heating temperature and heating time may be appropriately set depending on the type of crosslinking agent used, and are usually in the range of 20°C to 160°C and about 1 minute to 7 days. The heating for drying the solvent may also serve as the heating for crosslinking. The introduction of a crosslinked structure does not necessarily have to be accompanied by heating.
[0257] The first and second pressure-sensitive adhesive layers of the second embodiment preferably have the same thickness (thickness of each of the first and second pressure-sensitive adhesive layers, total thickness, thickness ratio), light transmittance, and shear storage modulus as the first and second pressure-sensitive adhesive layers of the first embodiment. The first and second pressure-sensitive adhesive layers of the second embodiment are not photocured, and therefore contain a photopolymerizable compound in an unreacted state. That is, the first and second pressure-sensitive adhesive layers of the second embodiment are photocurable pressure-sensitive adhesive layers containing a polymer, a photopolymerizable compound, a photopolymerization initiator, and, if necessary, a colorant.
[0258] The optical laminate having the photocurable first adhesive layer and / or second adhesive layer of the second form can be photocured by irradiating ultraviolet light after bonding with a display panel described later. Photocuring can change the adhesive strength between the optical laminate and the display panel. For example, since the adhesive layer before photocuring is highly flexible, it can fill in uneven shapes and steps formed by the light-emitting elements arranged on the display panel, and after photocuring, it can improve the adhesive strength and adhesive reliability to the display panel.
[0259] As the actinic radiation for photocuring the adhesive layer, ultraviolet rays are used. When an ultraviolet-transmitting colorant is used as in the adhesive layer of the first embodiment, the transmittance of ultraviolet rays is higher than that of visible light, so that photocuring inhibition can be suppressed even when the adhesive layer is thick.
[0260] The optical laminate having the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer of the first or second embodiment containing the ultraviolet-transmitting colorant has optical absorption in visible light. The optical laminate of the first or second embodiment preferably has a maximum transmittance at 350 nm to 450 nm.
[0261] The visible light transmittance of the optical laminate of the first and second embodiments is, for example, 80% or less, and may be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less.
[0262] [Third form] An optical laminate having a pressure-sensitive adhesive layer of the third form can be prepared by coating the solvent-based pressure-sensitive adhesive composition of the third form onto a release film, drying and removing the solvent as necessary to form a second pressure-sensitive adhesive layer, and attaching it to surface 3b of substrate 3. Next, the solvent-based pressure-sensitive adhesive composition of the third form is coated onto a release film, drying and removing the solvent as necessary to form a first pressure-sensitive adhesive layer, and then attaching it to the second pressure-sensitive adhesive layer laminated on surface 3b of substrate 3.
[0263] Alternatively, an optical laminate having a pressure-sensitive adhesive layer of the third form can be prepared by coating the solvent-based pressure-sensitive adhesive composition of the third form on the surface 3b of the substrate 3, and drying and removing the solvent as necessary to form a second pressure-sensitive adhesive layer. Next, the solvent-based pressure-sensitive adhesive composition of the third form is coated on a release film, and the solvent is dried and removed as necessary to form a first pressure-sensitive adhesive layer, and then bonding the first pressure-sensitive adhesive layer to the second pressure-sensitive adhesive layer laminated on the surface 3b of the substrate 3.
[0264] After the application of the solvent-based pressure-sensitive adhesive composition, the solvent is dried. As the drying method, a suitable method can be adopted as appropriate depending on the purpose. The heating and drying temperature is preferably 40°C to 200°C, more preferably 50°C to 180°C, and particularly preferably 70°C to 170°C. As the drying time, a suitable time can be adopted as appropriate. The drying time is preferably 5 seconds to 20 minutes, more preferably 5 seconds to 15 minutes, and particularly preferably 10 seconds to 10 minutes.
[0265] After coating the solvent-based pressure-sensitive adhesive composition, it may be heated as necessary. The heating temperature and heating time may be appropriately set depending on the type of crosslinking agent used, and are usually in the range of 20° C. to 160° C. and about 1 minute to 7 days.
[0266] It is preferable that the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer of the third embodiment have the same thickness (individual thickness, total thickness, and thickness ratio of the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer), light transmittance, and shear storage modulus as the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer of the first embodiment, respectively.
[0267] Furthermore, when the solvent-based pressure-sensitive adhesive composition contains (meth)acrylic block copolymer A, the storage modulus (G'25) at 25°C of the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer (particularly the first pressure-sensitive adhesive layer) is not particularly limited, but from the viewpoint of improving processability at room temperature, it is preferably 1 MPa or more, more preferably 1.5 MPa or more, more preferably 2 MPa or more, more preferably 2.5 MPa or more, and more preferably 3 MPa or more, and from the viewpoint of improving adhesive reliability at room temperature, it is preferably 50 MPa or less, more preferably 45 MPa or less, more preferably 40 MPa or less, more preferably 35 MPa or less, and more preferably 30 MPa or less.
[0268] When the solvent-based pressure-sensitive adhesive composition contains a (meth)acrylic block copolymer A, the storage modulus (G'50) at 50°C of the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer (particularly the first pressure-sensitive adhesive layer) is not particularly limited, but from the viewpoint of improving step absorbency in the range above 50°C, it is preferably 0.5 MPa or less, more preferably 0.45 MPa or less, more preferably 0.4 MPa or less, more preferably 0.35 MPa or more, and more preferably 0.3 MPa or less, and from the viewpoint of improving handleability in the range above 50°C, it is preferably 0.0001 MPa or more, more preferably 0.0005 MPa or more, more preferably 0.001 MPa or more, more preferably 0.005 MPa or more, and more preferably 0.01 MPa or more.
[0269] When the solvent-based pressure-sensitive adhesive composition contains a (meth)acrylic block copolymer A, the ratio of the storage modulus at 25°C to the storage modulus at 50°C (G'25 / G'50) of the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer (particularly the first pressure-sensitive adhesive layer) is not particularly limited, but from the viewpoint of improving processability at room temperature and improving step absorbency in the range above 50°C, it is preferably 3 or more, more preferably 5 or more, more preferably 10 or more, even more preferably 15 or more, and particularly preferably 20 or more, and from the viewpoint of adhesion reliability, handleability, etc., it is preferably 100 or less, more preferably 95 or less, more preferably 90 or less, even more preferably 85 or less, and particularly preferably 80 or less.
[0270] The storage modulus at 25° C. (G′25) and the storage modulus at 50° C. (G′25) and the ratio therebetween (G′25 / G′50) are measured by dynamic viscoelasticity measurement.
[0271] The optical laminate having the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer of the third type containing a colorant has optical absorption in visible light.
[0272] The visible light transmittance of the optical laminate of the third embodiment is, for example, 80% or less, and may be 70% or less, 60% or less, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less.
[0273] The optical laminate of the present embodiment (first to third embodiments) may have a release film provided on the first pressure-sensitive adhesive layer until use. The optical laminate of the present embodiment (first to third embodiments) may have a surface protective film laminated on the surface 3a of the substrate 3. The surface protective film is suitable for preventing scratches and adhesion of dirt during production, transportation, and shipping of the optical laminate and optical products including the optical laminate.
[0274] The optical laminate of the present embodiments (first to third embodiments) may have, in addition to the first pressure-sensitive adhesive layer 1, the second pressure-sensitive adhesive layer 2, the substrate 3, the release film, and the surface protective film, other layers, such as substrates other than the substrate 3, pressure-sensitive adhesive layers other than the first pressure-sensitive adhesive layer 1 and the second pressure-sensitive adhesive layer 2, intermediate layers, undercoat layers, etc., on the surface or between any layers, as long as the effects of the present invention are not impaired.
[0275] <Self-luminous display device> The self-luminous display device according to the second aspect of the present invention is a display device in which a large number of minute light-emitting elements are arranged on a wiring board, and each light-emitting element is selectively made to emit light by a light-emitting control means connected thereto, thereby directly displaying visual information such as characters, images, and videos on a display screen by blinking each light-emitting element. Examples of the self-luminous display device include mini / micro LED display devices and organic EL (electroluminescence) display devices. The optical laminate according to the first aspect of the present invention is particularly suitable for use in the manufacture of mini / micro LED display devices.
[0276] 4 to 6 are schematic diagrams (cross-sectional views) showing an embodiment of a self-luminous display device (mini / micro LED display device) according to the second aspect of the present invention. The mini / micro LED display device 20 according to this embodiment includes a display panel in which a plurality of LEDs 7 are arranged on one side of a substrate 5, and an optical laminate 10. The surface on which the LED chips 7 are arranged on the display panel and the first adhesive layer 1 of the optical laminate 10 are laminated. In the mini / micro LED display device 21, the surface 3a of the base material 3 on which the second adhesive layer 2 is not laminated is subjected to anti-reflection treatment and / or anti-glare treatment 4. In the mini / micro LED display device 22, the surface 3a of the base material 3 on which the second adhesive layer 2 is not laminated is formed with an anti-glare layer 4a as an anti-glare treatment.
[0277] In this embodiment, a metal wiring layer 6 for sending light emission control signals to each LED chip 7 is laminated on the substrate 5 of the display panel. The LED chips 7 emitting light of each color, red (R), green (G), and blue (B), are alternately arranged on the substrate 5 of the display panel via the metal wiring layer 6. The metal wiring layer 6 is made of a metal such as copper, and reflects the light emitted by each LED chip 7, reducing the visibility of the image. In addition, the light emitted by each LED chip 7 of each color of RGB is mixed, reducing the contrast.
[0278] In the mini / micro LED display device of this embodiment, the first adhesive layer 1 seals the spaces between the LED chips 7 arranged on the display panel and the metal wiring layer 6. The visible light transmittance of the first adhesive layer 1 is lower than that of the second adhesive layer 2, so that the first adhesive layer 1 has sufficient light blocking properties in the visible light range. The first adhesive layer 1, which has higher light blocking properties (low transparency), seals the spaces between the LED chips 7 without any gaps, so that it is possible to prevent color mixing between the LED chips 7 and improve contrast. In addition, the first adhesive layer 1, which has higher light blocking properties (low transparency), also seals the surface of the metal wiring layer 6, so that it is possible to prevent reflection by the metal wiring layer 6.
[0279] In this embodiment, the second adhesive layer 2 seals the upper part (display image side) of each LED chip 7 arranged on the display panel. The visible light transmittance of the second adhesive layer 2 is higher than that of the first adhesive layer 1, and therefore has sufficient transparency in the visible light region. Since the second adhesive layer 2, which has higher transparency, seals the upper part (display image side) of each LED chip 7, the absorption of visible light emitted from each LED chip 7 is suppressed to be low, and the light emission efficiency can be increased, so that the image can be made brighter. In addition, since there is no need to increase the output to increase the light emission brightness, power consumption can be kept low.
[0280] As described above, the optical laminate according to this embodiment includes a first pressure-sensitive adhesive layer having a higher light-shielding property (lower transmittance), and therefore, even when a metal adherend is laminated on the first pressure-sensitive adhesive layer, reflection and gloss of the metal surface can be prevented. When a metal adherend is laminated on the first pressure-sensitive adhesive layer of the optical laminate according to this embodiment, the reflectance of the visible light region of 5° regular reflection of the substrate surface 3a is preferably 50% or less, more preferably 30% or less, even more preferably 15% or less, and particularly preferably 10% or less. When a metal adherend is laminated on the first pressure-sensitive adhesive layer of the optical laminate according to this embodiment, the glossiness (based on JIS Z 8741-1997) of the substrate surface 3a is preferably 100% or less, more preferably 80% or less, even more preferably 60% or less, and particularly preferably 50% or less. The metal adherend may be made of copper, aluminum, stainless steel, or the like.
[0281] In addition, in the mini / micro LED display device of this embodiment, when the surface 3a of the substrate 3 is subjected to anti-reflection treatment and / or anti-glare treatment 4, the decrease in visibility due to reflection of external light or glare of images on the substrate surface 3a is prevented, or the appearance such as glossiness is adjusted. In the mini / micro LED display device 22 of this embodiment, an anti-glare layer 4a is formed on the surface 3a of the substrate 3. The average inclination angle θa (°) of the anti-glare layer 4a of the mini / micro LED display device 22 of this embodiment is the same as above.
[0282] The self-luminous display device of the present embodiment may include optical members other than the display panel and the optical laminate. Examples of the optical members include, but are not limited to, a polarizing plate, a retardation plate, an anti-reflection film, a viewing angle adjustment film, and an optical compensation film. The optical members also include members (such as a design film, a decorative film, and a surface protection plate) that play a role in decoration and protection while maintaining the visibility of the display device and the input device.
[0283] The mini / micro LED display device of this embodiment can be manufactured by bonding a display panel having a plurality of LED chips arranged on one side of a substrate to a first adhesive layer of the optical laminate according to the first aspect of the present invention.
[0284] Specifically, the display panel and the optical laminate having the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer of the first embodiment can be attached by laminating them under heat and / or pressure. When the display panel and the optical laminate having the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer of the second embodiment are attached, they can be laminated under heat and / or pressure and then photocured. The photocuring can be performed in the same manner as the photocuring to form the first pressure-sensitive adhesive layer and / or the second pressure-sensitive adhesive layer of the first embodiment described above.
[0285] When the first adhesive layer and / or the second adhesive layer is formed from a solvent-based adhesive composition containing a (meth)acrylic block copolymer A, the above lamination is preferably performed by heating and pressing at 50°C or higher. By heating and pressing at 50°C or higher, the adhesive layer becomes highly fluid, and can sufficiently follow the steps of the LED chips arranged on the substrate and adhere without gaps. Heating is performed at 50°C or higher, preferably 60°C or higher, more preferably 70°C or higher. Pressurization is not particularly limited, but is performed at, for example, 1.5 atm or higher, preferably 2 atm or higher, more preferably 3 atm or higher. Heating and pressing can be performed, for example, using an autoclave. The mini / micro LED display device manufactured in this way has a high storage modulus of the adhesive layer after being returned to room temperature (25°C), and has improved processability and adhesion reliability. EXAMPLES
[0286] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Various properties in the following production examples were evaluated or measured by the following methods.
[0287] (Surface shape measurement) A glass plate (thickness 1.3 mm) manufactured by Matsunami Glass Industrial Co., Ltd. was attached to the surface of the anti-glare film on which the anti-glare layer was not formed with an adhesive, and the surface shape of the anti-glare layer was measured using a high-precision fine shape measuring instrument (product name: Surfcorder ET4000, manufactured by Kosaka Laboratory Co., Ltd.) under the condition of a cutoff value of 0.8 mm, and the average inclination angle θa was obtained. The high-precision fine shape measuring instrument automatically calculates the average inclination angle θa. The average inclination angle θa is based on JIS B 0601 (1994 edition).
[0288] (Hayes) According to the method defined in JIS 7136, the anti-glare film was placed in a haze meter (manufactured by Murakami Color Research Laboratory, product name "HN-150") so that light was incident on the anti-glare layer surface, and the haze value was measured.
[0289] (Visible light transmittance of adhesive sheet) The release film on one side was peeled off from the adhesive sheet, and alkali-free glass was attached to the exposed surface. Thereafter, the release film on the other side was peeled off from the adhesive sheet, to obtain a sample in which the adhesive sheet was attached to the alkali-free glass plate. Using this sample, the transmission spectrum of the evaluation sample was measured with a visible-ultraviolet spectrophotometer (manufactured by Hitachi High-Technologies, product name "U-4100"). The alkali-free glass (single) was used as the baseline, and the ratio of the transmittance (amount of transmitted light) of the evaluation sample to the transmittance (amount of transmitted light) of the alkali-free glass was taken as the transmittance of the adhesive sheet. From the transmission spectrum of the adhesive sheet, the transmittance T VIS was calculated.
[0290] (Visible light transmittance of anti-glare film) The anti-glare film was placed in a spectrophotometer U4100 (Hitachi High-Technologies Corporation) so that light was incident from the anti-glare layer side, and the transmittance (%) in the visible light region was measured. This transmittance is the Y value measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for visibility.
[0291] Manufacturing Example 1 (Preparation of Anti-Glare Film) As the resin contained in the anti-glare layer, 100 parts by weight of ultraviolet-curable urethane acrylate resin (manufactured by DIC Corporation, product name "UNIDIC 17-806", solid content 80%) was prepared. Per 100 parts by weight of the resin solid content of the resin, 14 parts by weight of styrene crosslinked particles (manufactured by Soken Chemical & Chemical Industry Co., Ltd., product name "MX-350H", weight average particle size: 3.5 μm, refractive index 1.59) as light-diffusing fine particles, 2.5 parts by weight of synthetic smectite (manufactured by Kunimine Industries Co., Ltd., product name "Sumecton SAN") which is an organic clay as a thixotropy-imparting agent, 5 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "OMNIRAD907"), and 0.5 parts by weight of a leveling agent (manufactured by DIC Corporation, product name "Megafac F-556", solid content 100%) were mixed. This mixture was diluted with a mixed solvent of toluene / ethyl acetate (weight ratio 90 / 10) so that the solid content concentration was 30% by weight, to prepare a light diffusion element forming material (coating liquid). An anti-glare layer forming material (coating liquid) was applied to one side of a triacetyl cellulose (TAC) film (manufactured by Fujifilm Corporation, product name "TG60UL", thickness: 60 μm) capable of functioning as a protective layer using a bar coater to form a coating film. The transparent TAC film substrate on which this coating film was formed was then transported to a drying process. In the drying process, the coating film was dried by heating at 110°C for 1 minute. Thereafter, the coating film was dried using a high-pressure mercury lamp with an integrated light quantity of 300 mJ / cm2. 2 The coating film was irradiated with ultraviolet light of 1000 nm and cured to form a light diffusing element having a thickness of 5.0 μm on one side of the TAC film, thereby obtaining anti-glare film 1. The haze value of anti-glare film 1 was 42%. The θa (°) of the anti-glare layer of anti-glare film 1 was 1.22. The visible light transmittance of anti-glare film 1 was 90%.
[0292] Manufacturing Example 2 (Preparation of Anti-Glare Film) A light diffusion element was formed on one side of the TAC film in the same manner as in Production Example 1, to obtain antiglare film 2, except that 14 parts by weight of amorphous silica (manufactured by Fuji Silysia Chemical Co., Ltd., product name "Sylophobic 100", weight average particle size: 2.6 μm) was added as light diffusing fine particles and the thickness after curing treatment was set to 7.0 μm. The haze value of antiglare film 2 was 11%. The θa (°) of the antiglare layer of antiglare film 2 was 1.43. The visible light transmittance of antiglare film 2 was 91%.
[0293] Production Example 3 (Preparation of Anti-Glare Film) As the resin contained in the anti-glare layer forming material, 100 parts by weight of an ultraviolet-curable urethane acrylate resin (manufactured by DIC Corporation, product name "UNIDIC 17-806", solid content 80%) was prepared. As anti-glare layer forming particles, 7 parts by weight of amorphous silica (manufactured by Fuji Silysia Corporation, product name "Sylo Hobic 702"), 6.5 parts by weight of amorphous silica (manufactured by Fuji Silysia Corporation, product name "Sylo Hobic 100"), 5 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "OMNIRAD184"), and 0.5 parts by weight of a leveling agent (manufactured by DIC Corporation, product name "Megafac F-556") were mixed per 100 parts by weight of the resin solid content of the resin. This mixture was diluted with toluene so that the solid content concentration was 30%, to prepare an anti-glare layer forming material (coating liquid). A transparent plastic film substrate (TAC film, manufactured by Fujifilm Corporation, product name "TD80UL", thickness: 80 μm) was prepared as a light-transmitting substrate. The anti-glare layer-forming material (coating liquid) was applied to one side of the transparent plastic film substrate to form a coating film using a bar coater. The transparent plastic film substrate on which the coating film was formed was then transported to a drying process. In the drying process, the coating film was dried by heating at 110° C. for 1 minute. Thereafter, a high-pressure mercury lamp was used to apply an integrated light amount of 300 mJ / cm 2 . 2The coating film was irradiated with ultraviolet light of 1000 u.s. and cured to form an anti-glare layer having a thickness of 5.0 μm, thereby obtaining anti-glare film 3. The θa (°) of the anti-glare layer of anti-glare film 3 was 3.5. The visible light transmittance of anti-glare film 3 was 91%.
[0294] Production Example 4 (Preparation of Anti-Glare Film) Anti-glare film 4 was obtained in the same manner as in Production Example 3, except that 6.5 parts by weight of amorphous silica (manufactured by Fuji Silysia Co., Ltd., product name "Sylo Hobic 702") and 6.5 parts by weight of amorphous silica (manufactured by Fuji Silysia Co., Ltd., product name "Sylo Hobic 200") were added as anti-glare layer forming particles, and 2.5 parts by weight of a thickener (manufactured by Co-op Chemical, product name "Lucentite SAN") were added, and the thickness after curing treatment was 8.0 μm. The θa (°) of the anti-glare layer of anti-glare film 4 was 2.3. The visible light transmittance of anti-glare film 4 was 91%.
[0295] Production Example 5 (Preparation of Prepolymer) Into a separable flask equipped with a thermometer, a stirrer, a reflux condenser, and a nitrogen gas inlet tube, 67 parts by weight of butyl acrylate (BA), 14 parts by weight of cyclohexyl acrylate (CHA, manufactured by Osaka Organic Chemical Industry Co., Ltd., product name "Viscoat #155"), 19 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.09 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "Irgacure 184"), and 0.09 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "Irgacure 651") were added, and then nitrogen gas was introduced and replaced with nitrogen for about 1 hour while stirring. After that, 5 mW / cm 2 The reaction rate was adjusted to 5-15%, and an acrylic prepolymer solution was obtained.
[0296] Production Example 6 (Preparation of Polymer RAFT Solution A1) A reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer, and a stirrer was charged with 50 parts by weight of cyclohexyl acrylate (CHA) and 50 parts by weight of 3,3,5-trimethylcyclohexyl acrylate (TMCHA) as monomer components, 0.5 parts by weight of dibenzyl trithiocarbonate (DBTC) as a RAFT agent, and 100 parts by weight of ethyl acetate as a polymerization solvent. 0.2 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) was then added as a thermal polymerization initiator, and solution polymerization was carried out under a nitrogen atmosphere to obtain a polymer RAFT solution A1 with a Mw of 180,000. (Preparation of acrylic triblock copolymer-containing adhesive solution B1) A reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer, and a stirrer was charged with 97 parts by weight of 2-ethylhexyl acrylate (2EHA), 3 parts by weight of 4-hydroxybutyl acrylate (4HBA) as monomer components, 100 parts by weight of the polymer RAFT solution A1 obtained above, and 100 parts by weight of ethyl acetate as a polymerization solvent. 0.2 parts by weight of 2,2'-azobisisobutyronitrile (AIBN) was then added as a thermal polymerization initiator and solution polymerization was carried out under a nitrogen atmosphere to obtain an adhesive solution B1 containing an ABA-type acrylic triblock copolymer with Mw of 400,000 and Mw / Mn of 4.3. In the calculated glass transition temperature (Tg) according to the FOX formula, the Tg of segment A of the ABA type acrylic triblock copolymer is 32°C, and the Tg of segment B is -70°C. The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the above product were measured in terms of standard polystyrene by gel permeation chromatography (GCP method) under the following measurement conditions. Measuring device: HLC-8320GPC (Tosoh Corporation) Column: TSKgelGMH-H(S), (Tosoh Corporation) Mobile phase solvent: Tetrahydrofuran ·Flow rate: 1.0cm 3 / min Column temperature: 40℃
[0297] Production Example 7 (Preparation of black adhesive composition) To the acrylic prepolymer solution obtained in Production Example 7 (total amount of prepolymer is taken as 100 parts by weight), 9 parts by weight of 2-hydroxyethyl acrylate (HEA), 8 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.02 parts by weight of dipentaerythritol hexaacrylate (manufactured by Shin-Nakamura Kogyo Kagaku, product name "KAYARAD DPHA") as a polyfunctional monomer, 0.35 parts by weight of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent, and 0.3 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "Irgacure 651") were added to prepare a photopolymerizable adhesive composition solution. To 100 parts by weight of the photopolymerizable adhesive composition solution obtained above, 0.2 parts by weight of a photopolymerization initiator (manufactured by BASF, product name "Irgacure 651") and 4 parts by weight of a black pigment dispersion (manufactured by Tokushiki Corporation, product name "Tokushiki 9050 Black") were added to prepare a photopolymerizable black adhesive composition solution.
[0298] Production Example 8 (Preparation of black adhesive composition) A black solvent-type adhesive composition solution was prepared by adding 2 parts by weight of a black dye ("VALIFAST BLACK 3810" manufactured by Orient Chemical Industry Co., Ltd.) per 100 parts by weight of the total amount of monomers used in Preparation Example 6 to the adhesive solution B1 containing the acrylic triblock copolymer obtained in Preparation Example 6.
[0299] Production Example 9 (Preparation of Pressure-Sensitive Adhesive Composition) To the acrylic prepolymer solution obtained in Production Example 5 (total amount of prepolymer is taken as 100 parts by weight), 9 parts by weight of 2-hydroxyethyl acrylate (HEA), 8 parts by weight of 4-hydroxybutyl acrylate (4-HBA), 0.12 parts by weight of dipentaerythritol hexaacrylate (manufactured by Shin-Nakamura Kogyo Kagaku, product name "KAYARAD DPHA") as a polyfunctional monomer, and 0.35 parts by weight of 3-glycidoxypropyltrimethoxysilane as a silane coupling agent were added to prepare a photopolymerizable pressure-sensitive adhesive composition solution.
[0300] Manufacturing Example 10 (Preparation of Adhesive Sheet) The black adhesive composition solution prepared in Production Example 7 was applied to the release surface of a 38 μm-thick release film R1 (manufactured by Mitsubishi Plastics, Inc., product name "MRF#38"), one side of which is a polyester film, so that the thickness after curing would be 50 μm, and the black adhesive composition solution prepared in Production Example 7 was applied to the release surface of the ...2 (manufactured by Mitsubishi Plastics, Inc., MRE#38), one side of which is a polyester film, so that the black adhesive composition solution prepared in Production Example 7 was applied to the release surface of the release film R1 (manufactured by Mitsubishi Plastics, Inc., product name "FL15BL"), one side of which is a polyester film, so that the thickness after curing would be 50 μm. 2 , cumulative light intensity 1300mJ / cm 2 As a result, a 50 μm-thick adhesive sheet 1 in the form of a substrate-less adhesive sheet was obtained in which a photocrosslinkable adhesive, which was a cured product of the black adhesive composition, was sandwiched between the release films R1 and R2. The above black light illuminance values are values measured using an industrial UV checker (manufactured by Topcon Corporation, product name: UVR-T1, light receiving unit model: UD-T36) with a peak sensitivity wavelength of about 350 nm. The visible light transmittance of the pressure-sensitive adhesive sheet 1 was 40%.
[0301] Manufacturing Example 11 (Preparation of Adhesive Sheet) In the same manner as in Production Example 10, except that the coating was performed so that the thickness after curing would be 100 μm, a 100 μm-thick adhesive sheet 2 in the form of a substrateless adhesive sheet was obtained in which a photocrosslinkable adhesive, which is a cured product of the black adhesive composition, was sandwiched between release films R1 and R2. The visible light transmittance of the adhesive sheet 2 was 16%.
[0302] Manufacturing Example 12 (Preparation of Adhesive Sheet) Except for coating so that the thickness after curing was 150 μm, a 150 μm-thick adhesive sheet 3 was obtained in the form of a substrateless adhesive sheet, in which a photocrosslinkable adhesive, which is a cured product of the black adhesive composition, was sandwiched between release films R1 and R2, in the same manner as in Production Example 10. The visible light transmittance of the adhesive sheet 3 was 3%.
[0303] Manufacturing Example 13 (Preparation of Adhesive Sheet) A 75 μm thick polyethylene terephthalate (PET) film ("Diafoil MRF75" manufactured by Mitsubishi Chemical) with a silicone-based release layer on its surface was used as a substrate, and the black solvent-based adhesive composition solution prepared in Production Example 8 was applied onto the substrate and dried at 130° C. for 3 minutes to form an adhesive layer with a thickness of 50 μm. A 75 μm thick PET film ("Diafoil MRE75" manufactured by Mitsubishi Chemical) with one side treated with silicone release was laminated onto this adhesive layer to obtain an adhesive sheet 4 with release films on both sides in the form of a substrate-less adhesive sheet. The visible light transmittance of the adhesive sheet 4 was less than 1%.
[0304] Manufacturing Example 14 (Preparation of Adhesive Sheet) Except for applying the black solvent-type adhesive composition solution prepared in Preparation Example 8 so that the thickness after drying was 75 μm, a 75 μm-thick adhesive sheet 5 in the form of a substrateless adhesive sheet was obtained in the same manner as in Preparation Example 13, in which an adhesive layer of the black solvent-type adhesive composition was sandwiched between release films. The visible light transmittance of the adhesive sheet 5 was less than 1%.
[0305] Manufacturing Example 15 (Preparation of Adhesive Sheet) Except for applying the black solvent-type adhesive composition solution prepared in Preparation Example 8 so that the thickness after drying was 100 μm, a 100 μm-thick adhesive sheet 6 in the form of a substrateless adhesive sheet was obtained in the same manner as in Preparation Example 13, in which an adhesive layer of the black solvent-type adhesive composition was sandwiched between release films. The visible light transmittance of the adhesive sheet 6 was less than 1%.
[0306] Manufacturing Example 16 (Preparation of Adhesive Sheet) Except for applying the adhesive composition solution prepared in Preparation Example 9 so that the thickness after curing was 100 μm, a 100 μm-thick adhesive sheet 7 was obtained in the form of a substrateless adhesive sheet, in which a photocrosslinkable adhesive, which is a cured product of the adhesive composition, was sandwiched between release films R1 and R2, in the same manner as in Preparation Example 10. The visible light transmittance of the adhesive sheet 7 was 90%.
[0307] Manufacturing Example 17 (Preparation of Adhesive Sheet) Except for applying the adhesive composition solution prepared in Preparation Example 9 so that the thickness after curing was 200 μm, a 200 μm-thick adhesive sheet 8 in the form of a substrateless adhesive sheet was obtained in the same manner as in Preparation Example 10, in which a photocrosslinkable adhesive, which is a cured product of the adhesive composition, is sandwiched between release films R1 and R2. The visible light transmittance of the adhesive sheet 8 was 90%.
[0308] Example 1 (Preparation of Optical Laminate) One release film was peeled off from the adhesive sheet 8 obtained in Production Example 17 cut to 20 mm x 20 mm, and the exposed adhesive surface was attached to the center of a 45 mm x 50 mm glass plate (visible light transmittance: 93%), and then the other release film was peeled off to expose the adhesive surface. One release film was peeled off from the adhesive sheet 1 obtained in Production Example 10 cut to 20 mm x 20 mm, and the exposed adhesive surface was attached to the adhesive surface of the adhesive sheet 8, to obtain an optical laminate 1 consisting of glass plate / adhesive sheet 8 / adhesive sheet 1 / release film.
[0309] Examples 2 to 6 (Preparation of Optical Laminate) Except for using adhesive sheets 2 to 6 instead of adhesive sheet 1, the same procedure as in Example 1 was carried out to obtain optical laminates 2 to 6 each consisting of glass plate / adhesive sheet 8 / adhesive sheets 2 to 6 / release film.
[0310] Comparative Example 1 (Preparation of Optical Laminate) Except for using adhesive sheet 7 instead of adhesive sheet 1, the same procedure as in Example 1 was carried out to obtain optical laminate 7 each consisting of glass plate / adhesive sheet 8 / adhesive sheet 7 / release film.
[0311] (evaluation) The optical laminates obtained in the above Examples and Comparative Examples were subjected to the following evaluations. The evaluation methods are shown below.
[0312] (1) Evaluation of step-following ability (Preparation of uneven substrate) A laminate of TAC film (thickness 60 μm) and adhesive (thickness 20 μm) was bonded to a 45 mm x 50 mm glass plate, and then a CO2 laser (wavelength 10.6 μm, laser diameter 〇 μm) was used to perform linear etching within a central 10 mm x 10 mm area at a vertical pitch of 150 μm and a horizontal pitch of 225 μm, resulting in adherend A, in which the TAC film and adhesive layer were processed into a lattice-like uneven shape. This adherend A imitates an LED panel in which multiple LED films are arranged on a substrate. (Vacuum bonding) The release films of the optical laminates 1 to 7 prepared in Examples 1 to 6 and Comparative Example 1 were peeled off to expose the adhesive surfaces, which were then bonded to the processed surface of adherend A using a vacuum bonding device (CRIMB Products, SE340aaH) with a precision such that the adhesive sheet could completely cover the processed area of adherend A, to obtain evaluation samples 1 to 7, each consisting of glass plate / adhesive sheet 8 / adhesive sheets 1 to 7 / adherend A. (Evaluation of step-following ability) In evaluation samples 1 to 7, when the adhesive sheet is able to conform to the uneven pattern portion, the processed portion of the adherend A appears transparent, and the portion that cannot be conformed appears white. Taking advantage of this property, the area of the white portion was calculated by photographing with a fixed camera to evaluate the ability to conform to steps. Level difference conformity (%) = 100 - {[area of white area during evaluation] / [area of white area before lamination = 1 cm 2 ]×100} The step conformability was measured immediately after lamination and after autoclaving (at 50°C and 0.5 MPa for 15, 30, and 60 minutes). The results are shown in Table 1.
[0313] [Table 1]
[0314] (2)Visible light transmittance The optical laminates obtained in the above examples and comparative examples were placed in a spectrophotometer U4100 (manufactured by Hitachi High-Technologies Corporation) so that light was incident from the glass plate side, and the transmittance (%) in the visible light region was measured. This transmittance is the Y value measured using a 2-degree visual field (C light source) according to JIS Z8701 and corrected for visibility. The results are shown in Table 2.
[0315] (3)Reflectance A plate was prepared by laminating aluminum foil on a black acrylic plate. The release film of the optical laminate obtained in the above examples and comparative examples was peeled off, and the exposed adhesive surface was laminated on the aluminum foil side of the plate to prepare a sample. The obtained sample was placed in a spectrophotometer U4100 (manufactured by Hitachi High-Technologies Corporation) with the anti-glare film / TAC film on the light source side, and the reflectance (%) of the visible light region at 5° regular reflection was measured.
[0316] [Table 2]
[0317] Example 7 (Preparation of Optical Laminate) One release film is peeled off from the adhesive sheet 8 obtained in Production Example 17 cut to 20 mm x 20 mm, and the exposed adhesive surface is attached to the center of the surface of the anti-glare film 1 obtained in Production Example 1 cut to 45 mm x 50 mm where the anti-glare layer is not formed, and then the other release film is peeled off to expose the adhesive surface. One release film is peeled off from the adhesive sheet 1 obtained in Production Example 10 cut to 20 mm x 20 mm, and the exposed adhesive surface is attached to the adhesive surface of the adhesive sheet 8, to obtain an optical laminate 8 consisting of the anti-glare film 1 / adhesive sheet 8 / adhesive sheet 1 / release film.
[0318] Examples 8 to 10 (Preparation of Optical Laminate) Except for using the antiglare films 2 to 4 obtained in Production Examples 2 to 4 instead of the antiglare film 1, the same procedure as in Example 7 is repeated to obtain optical laminates 9 to 11 each consisting of the antiglare films 2 to 4 / adhesive sheet 8 / adhesive sheet 1 / release film. [Explanation of symbols]
[0319] 10, 11, 12 Optical laminate 1 First adhesive layer 2 Second adhesive layer 3 Base material 4. Anti-reflective and / or anti-glare treatment 4a Anti-glare layer 20, 21, 22 Self-luminous display device (mini / micro LED display device) 5 Substrate 6 Metal wiring layer 7 Light emitting element (LED chip)
Claims
1. a laminated structure in which a first pressure-sensitive adhesive layer, a second pressure-sensitive adhesive layer, and a base material are laminated in this order; The visible light transmittance T of the first pressure-sensitive adhesive layer 1 and the visible light transmittance T of the second pressure-sensitive adhesive layer 2 , T 1 <T 2 Fills the gap, An optical laminate, wherein the surface of the substrate on which the second adhesive layer is not laminated is anti-reflection treated and / or anti-glare treated (the optical laminate excludes optical laminates in which the total light transmittance changes in the transverse direction of the optical laminate).
2. The visible light transmittance T of the first pressure-sensitive adhesive layer 1 , and the visible light transmittance T of the base material 3 , T 1 <T 3 The optical laminate according to claim 1 ,
3. The visible light transmittance T of the first pressure-sensitive adhesive layer 1 The optical laminate according to claim 1 or 2, wherein the optical transparency is 80% or less.
4. The visible light transmittance T of the second pressure-sensitive adhesive layer 2 The optical laminate according to any one of claims 1 to 3, wherein the optical coefficient of curvature is 85 to 100%.
5. The optical laminate according to any one of claims 1 to 4, wherein the first pressure-sensitive adhesive layer and the second pressure-sensitive adhesive layer are pressure-sensitive adhesive layers formed from a pressure-sensitive adhesive composition selected from a photocurable pressure-sensitive adhesive composition and a solvent-based pressure-sensitive adhesive composition.
6. The optical laminate according to claim 5 , wherein the pressure-sensitive adhesive composition forming the first pressure-sensitive adhesive layer contains a colorant.
7. The optical laminate according to claim 5 , wherein the pressure-sensitive adhesive composition contains an acrylic polymer.
8. The optical laminate according to claim 7 , wherein the acrylic polymer contains a (meth)acrylic block copolymer.
9. The optical laminate according to claim 8 , wherein the pressure-sensitive adhesive composition forming the first pressure-sensitive adhesive layer is a solvent-based pressure-sensitive adhesive composition containing a (meth)acrylic block copolymer.
10. The optical laminate according to any one of claims 1 to 9, wherein the first pressure-sensitive adhesive layer has a thickness of 10 to 300 µm.
11. The optical laminate according to any one of claims 1 to 10, wherein the second pressure-sensitive adhesive layer has a thickness of 1 to 500 µm.
12. The optical laminate according to any one of claims 1 to 11, wherein the ratio of the thickness of the second pressure-sensitive adhesive layer to the thickness of the first pressure-sensitive adhesive layer (thickness of the second pressure-sensitive adhesive layer / thickness of the first pressure-sensitive adhesive layer) is 1.0 to 5.
0.
13. The optical laminate according to any one of claims 1 to 12, wherein the anti-glare treatment is an anti-glare layer provided on one side of the substrate.
14. the anti-glare layer is formed using an anti-glare layer-forming material including a resin, particles, and a thixotropy-imparting agent; The optical laminate according to claim 13, wherein the antiglare layer has aggregated portions in which the particles and the thixotropy-imparting agent aggregate to form convex portions on a surface of the antiglare layer.
15. The optical laminate according to claim 14, wherein the average inclination angle θa (°) of the convex portions on the surface of the antiglare layer is in the range of 0.1 to 1.
5.
16. The optical laminate according to any one of claims 1 to 15, further comprising a surface protection film laminated on the surface of the substrate on which the second pressure-sensitive adhesive layer is not laminated.
17. A display panel having a plurality of light-emitting elements arranged on one surface of a substrate; A self-luminous display device comprising the optical laminate according to any one of claims 1 to 16, A self-luminous display device, in which the surface of the display panel on which light-emitting elements are arranged and the first adhesive layer of the optical laminate are laminated.
18. 18. The self-luminous display device according to claim 17, wherein the display panel is an LED panel having a plurality of LED chips arranged on one surface of a substrate.
Citation Information
Patent Citations
Functional laminated film, method for manufacturing the same, and crt having the film bonded thereto
JP2001334608A
Light absorption layer contained in color filter for organic electroluminescence display and sheet using the same
JP2017203810A
display device
JP2018523854A
Self-luminous display
JP2019204905A
Adhesive sheet and display body
JP2020169262A